Catalytic performance of metal-free ethylenediammonium salt catalysts in the thermal decomposition of ammonium perchlorate - Mei-Qing Lai; Jun Hu; Bo-Wen Fan; Wen-Jing Yang; Jian-Gang Xu; Meng Cui; Guo-Cong Guo (Fuel, 2027)

Mechanochemical grafting polymerization of fluorinated thioctic acid towards high-performance aluminum fuels - Chen Wang; Cong Luo; Lu Liu; Ruoqing Zhao; Yanfeng Jiang; Xiaoyu Wang; Wenru Fan; Wei Li; Wen Ao; Zhenhua Wang (Fuel, 2026)

Real-time intelligent colorimetric paper indicator based on a mulberry-derived anthocyanin for monitoring aquatic products freshness - Guangxin Yang; Junyu Zhang; Yifan Zhao; Lin Gu; Peng Wang; Chengqi Fan; Hai Chi; Cong Kong (Food Packaging and Shelf Life, 2026)

Rational design of a cold-adapted denitrifying consortium reveals synergistic mechanisms for enhanced low-temperature wastewater treatment - Hai Zhen Jing; Xiao Lan Ren; Cong Shen; Jia Jing Chen; Duan Yun; Yuan Jin; Xiao Jun Fan (Bioresource Technology, 2026)

Unveiling microscale aerosol formation pathways in combustion systems: in situ evidence from cigarette burning cones - Jiaying Li; Huapeng Cui; Meijuan Fan; Li Chen; Yaqiong Qin; Ruihong Liu; Mantang Chen; Yu Liu; Jizhao Guo; Shaofeng Liu; Xiaobing Zhang; Fuwei Xie; et al. (Biomass and Bioenergy, 2026)

TFR2 p.A75V mutation aggravates liver iron overload in alcoholic liver disease via ERK pathway - Chao Xie; Yingying Liu; Xiaofan Wang; Long Huang; Xiaoming Wang; Wei Zhang; Lina Wu; Tianhui Liu; Ping Wang; Lin Liu; Xu Fan; Jidong Jia; et al. (Journal of Molecular Medicine, 2026)

Mechanistic insights into WRKY transcription factor-mediated regulation of fruit pigmentation - ZhiTong Zhou; TingTing Li; ZhiCheng Yan; KaiPing Cong; CaiE Wu; GongJian Fan; XiaoJing Li; DanDan Zhou; YiQing Zhu (Plant Science, 2026)

Over-expression of the solute carrier gene SLC23A1 as a novel mechanism contributing to imidacloprid resistance in Nilaparvata lugens - Fan Zhang; Zhi-Tao Yu; Yan-Chao Zhang; Yu-Qiu Xie; Li-Xiang Wang; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2026)

A natural Nlscarlet insertion underlies the orange-eye phenotype and facilitates efficient multiple-sgRNA genome editing in Nilaparvata lugens - Wen-Nan Ye; Rong-Yu Chen; Qi Xing; Yan-Chao Zhang; Shun-Fan Wu; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2026)

Structure and functional properties of Dendrobium officinale polysaccharide-hemp seed protein gels for dysphagia diets as regulated by alkali concentration and temperature - Tingting Ding; Jing Sun; Qingquan Ma; Shuqi Gao; Cong Lu; Jiameng Liu; Fengzhong Wang; Bei Fan (Food Research International, 2026)

A multi-herb botanical formula ameliorates diet-induced non-alcoholic fatty liver disease associated with microbiota-dependent metabolic remodeling in mice - Xinrui Meng; Fan Wang; Ying Li; Yan Li; Meiping Zhang; Jing Cong (Food Research International, 2026)

Rapid preliminary screening of amine absorbents for post-combustion CO2 capture - Xi Tang; Bin Xu; Xiaoyi Gao; Xiaoshan Li; Ge Gao; Wen Chen; Fan Wu; Cong Luo; Liqi Zhang (Chemical Engineering Journal, 2026)

Influences of stoss-face opening configurations on irregular wave energy partition and frequency dependence across reef structures: Laboratory investigation - Hongyi Li; Cuiping Kuang; Jilong Chen; Wei Xing; Xin Cong; Jiadong Fan; Qingping Zou (Ocean Engineering, 2026)

Experimental study on combined dust suppression and ecological restoration by microbially induced carbonate precipitation and ryegrass - Yanyun Zhao; Yanli Cong; Xiangming Hu; Yue Feng; Xueying Fan; Jingqian Wang (Journal of Environmental Chemical Engineering, 2026)

An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

Comparison of porcine reproductive and respiratory syndrome modified live virus and inactivated virus vaccines against NADC34-like PRRS virus challenge in the field - Zhaojun Wang; Cong Jin; Huixia Fan; Shuai Zhang; Yunhuan Zhao; Jinghui Fan; Yuzhu Zuo (Veterinary Research Communications, 2026)

Heterogeneous root zone salinity mitigates salt hazards through the regulation of rhizosphere microorganisms and root metabolites in cucumber - Xingchen Liu; Changxia Du; Wangwang Xu; Lu Wang; Yinqing Tan; Cong Yue; Huaifu Fan (Soil Ecology Letters, 2026)

Internal solitary waves-sloping seabed interaction induced sediment resuspension and seabed multiparameter responses - Cong Hu; Chenglong Zhou; Xiuyao Fan; Chenwei Lu; Chang Su; Tingjie Xu; Mengxue Liu (Advances in Water Resources, 2026)

Field resistance monitoring and nAChR α6 target validation support spinetoram as a candidate insecticide for rotation in Nilaparvata lugens resistance management - Wen-Nan Ye; Qi Xing; Rong-Yu Chen; Yan-Chao Zhang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Decoupling effect of fulvic acid on Fe(II)-mediated transformation of Cr(VI)-loaded lepidocrocite: Enhanced Cr immobilization independent of mineral transformation - Cong Fan; Wenwu Pan; Limiao Cai; Yan Yang; Qian Yao; Xiaohu Jin; Xiaofei Li; Chuling Guo; Fenglan Lu; Bing Zhang; Zhi Dang (Environmental Pollution, 2026)

Selective confinement of KOH within activated carbon cloth: A strategy for fast, low-temperature regenerable direct air capture - Kai Tang; Haoqian Chen; Yuxiang Wu; Xiaoshan Li; Cong Luo; Liqi Zhang; Fan Wu (Chemical Engineering Journal, 2026)

Interface-engineered ZrO2@Co3O4 core-shell materials from bimetallic MOFs for enhanced room temperature NO2 sensing - Jiahui Fan; Xiaopeng Wang; Shanshan Cong; Rui Zhang; Weixin Lv; Li Li; Qingjiang Pan; Xue Bai; Keying Shi (Chemical Engineering Journal, 2026)

Sex- and size-dependent impacts of tire wear particles and zinc oxide nanoparticles on adult zebrafish: integrated evidence from physiology, gut microbiota networks, and hepatic transcriptomics - Fan Wang; Xinrui Meng; Qianqian Song; Jing Cong (Chemico-Biological Interactions, 2026)

Three New Arnebin-type metabolites extracted from Arnebia euchroma: Structural analysis and antitumor activity evaluation - Guang-Jie Pan; Yu Sun; De-Gang Qing; Cong-Zhao Fan; Guo-Xu Ma; Zhong-Hao Sun; Lei-Ling Shi; Jing Zhang (Phytochemistry Letters, 2026)

Irregular-wave transformation over an open-top artificial reef with low-opening-ratio baffles under variable relative submergence - Hongyi Li; Cuiping Kuang; Jiadong Fan; Jilong Chen; Xin Cong; Lin Li (Ocean Engineering, 2026)

A multi-physics digital twin-enhanced meta-learning framework for multi-mode coupled failure in offshore wind-powered hydrogen production systems - Cong Li; Jixin Zhang; Yuqin Wang; Siyuan Liu; Yutong Hou; Fan Liu; Qiuju You (Ocean Engineering, 2026)

Transcriptomic and physiological insights into 1-MCP–mediated delay of postharvest senescence in fresh goji berries under immediate and post-transport treatments - Fei Yao; Tingting Li; Jie Shi; Yafei Li; Li Jiang; Zhicheng Yan; Caie Wu; Gongjian Fan; Xiaojing Li; Dandan Zhou; Kaiping Cong (Food Bioscience, 2026)

Deactivation boundaries and structural evolution of CaO sorbents under prolonged high-temperature calcination for calcium looping CO₂ capture - Zhaowei Shi; Cong Luo; Huizhe Wu; Penghui Yang; Donglong Lai; Zewu Zhang; Fan Wu; Xiaoshan Li; Liqi Zhang (Chemical Engineering Journal, 2026)

Source tracing of enhanced sediment loss and its seasonal shifts in a degrading permafrost catchment - Jiawei Su; Fan Zhang; Chao Liu; Rensheng Chen; Cong Chen; Ying Zheng; Yang Zhao; Chen Zeng; Kiran Bishwakarma; Jianhang Zhu; Shaopeng Gao; Xiaonan Shi (CATENA, 2026)

NPY-Y2R driven neuroimmune signaling as a potential therapeutic target for trigeminal neuralgia: clinical and experimental evidence - Zi-Le He; Chao Xu; Qi-Fan Yang; Cong-Zhou Han; Ting Wu; Yu-Qing Xu; Yun-Ze Liu; Liang-Yu Ni; Si-Qi Jia; Tang-Yu Zhang; Yun Wang; Yi Feng (Science Bulletin, 2026)

Optimized crop management enhances sweet maize yield and reduces reactive nitrogen losses in a rainfall-uneven, water-sensitive region of Southwest China - Feiyu Ying; Shuo Pan; Zhiwei Fan; Xingbang Wang; Zhibing Lv; Ziming Tian; Xiaokang Hu; Kadambot.H.M. Siddique; Fusuo Zhang; Wen-Feng Cong (European Journal of Agronomy, 2026)

Molecular fractionation of dissolved organic matter: A governing mechanism for the coupled fate of phosphorus and chromium at iron mineral interfaces - Cong Fan; Zhoumei Hu; Qian Yao; Limiao Cai; Bing Zhang; Xiaohu Jin; Yu Liu; Chuling Guo; Guining Lu; Xiaofei Li; Zhi Dang (Chemical Engineering Journal, 2026)

Mechanistic insights into glufosinate-ammonium (GLA)-Induced brain injury revealed by LC-MS/MS-based metabolomics - Huan-le Ye; Xin-xin Zheng; Mian-mian Li; Zhi-qiang Zhang; Liu-xu Chen; Wen-jing Zhang; Ren Cheng-Han Fan; Guo-xin He; An-cong Xu (Chemico-Biological Interactions, 2026)

Experimental study of wave propagation over a vegetated ecological artificial reef - Hongyi Li; Cuiping Kuang; Jiadong Fan; Wei Xing; Jilong Chen; Xin Cong (Coastal Engineering, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Enhancing CO2 capture performance of K2CO3 derived from KHCO3 precursor via dispersion on non-porous SiO2 - Ziqiang Han; Cong Luo; Xiaoshan Li; Zhen Du; Zewu Zhang; Fan Wu; Liqi Zhang (Journal of Environmental Chemical Engineering, 2026)

Gender-specific association between household cooking oil fumes exposure and small airway dysfunction in China: a national cross-sectional study - Wenjing Wang; Shu Cong; Shige Qi; Jing Fan; Xuping Song; Qi Luo; Ning Wang; Liwen Fang (Environmental Pollution, 2026)

A new rainfall nowcasting method by introducing the attention mechanism into the ConvGRU deep learning model - Mingkun Su; Wenjie Yuan; Zhihao Lai; Cong Chen; Junyao Du; Yourui Fan; Wenqin Deng (Theoretical and Applied Climatology, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

Nonlinear drivers of canopy and surface urban heat islands across China’s climate zones: marginal and interaction effects from explainable machine learning - Cong Wen; Ali Mamtimin; Haitao Wang; Yu Wang; Haotong Liu; Hajigul Sayit; Meiqi Song; Jiacheng Gao; Ailiyaer Aihaiti; Yisilamu Wulayin; Fan Yang; Chenglong Zhou; et al. (Sustainable Cities and Society, 2026)

Calcium-based pellets prepared by coal fly ash and cement Co-supporting method for CO2 capture - Dingmingyang Hou; Cong Luo; Zhen Du; Xiaoshan Li; Fan Wu; Liqi Zhang (Fuel, 2026)

Divergent redistribution behavior of arsenic and antimony during schwertmannite transformation in presence of cysteine - Miaosha Cheng; Qi Huang; Xiaohu Jin; Qian Yao; Cong Fan; Xiaofei Li; Lijuan Zeng; Haiming Cai; Xueqin Tao; Guining Lu; Zhi Dang (Environmental Pollution, 2026)

Observed and modeled interactions between atmospheric pollutants and urban thermal environment in an arid city: Urumqi as a case study - Cong Wen; Yu Wang; Ali Mamtimin; Jian Peng; Hajigul Sayit; Jiali Feng; Meiqi Song; Jiacheng Gao; Ailiyaer Aihaiti; Junjian Liu; Yisilamu Wulayin; Chenglong Zhou; et al. (Atmospheric Environment, 2026)

The interactive effects of roasting degree and lipid content on the gas retention capacity in fermented oat dough - Fan Yang; Wenhua Ma; Ruige Yu; Binghua Sun; Xiaojie Qian; Cong Sun; Chong Liu; Sen Ma; Xiaoxi Wang (Food Research International, 2026)

Insight into the mechanism of natural preservatives (rosmarinic acid and phytic acid) against quality deterioration of Pacific white shrimp through interactions with hemocyanin - Junpeng Zeng; Xiaowei Fan; Junyi Song; Yu Song; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2026)

Ball milling assisted Al/Si co-doping for enhanced performance of calcium-based CO2 adsorbents: Structural evolution and synergistic mechanisms - Penghui Yang; Cong Luo; Huizhe Wu; Zhen Du; Bo Liu; Xiaoshan Li; Fan Wu; Zewu Zhang; Liqi Zhang (Chemical Engineering Journal, 2026)

Defect-rich 3D flower-like SnS2-xSex nanostructures for ultrasensitive NO2 gas sensing at room temperature - Shanshan Cong; Pengkai Xing; Wenbo Ruan; Jiahui Fan; Xiaopeng Wang; Rui Zhang; Weixin Lv; Qin Guo; Xue Bai; Keying Shi (Chemical Engineering Journal, 2026)

Application of ENU-mediated efficient mutagenesis in breeding of the big belly seahorse (Hippocampus abdominalis) - Xiao-lei Su; Chun-yu Hou; Lin Shi; Shi-chang Zhang; Cheng-de Fan; Jie-zhou Wang; Yi-cong Ma; Wu-hong Lv; Cong Liu; Guo-dong Zheng; Kai Wang (Aquaculture, 2026)

Potential for improving micronutrient supply and environmental sustainability by using underutilized crops in China - Yijun Li; Johanna C. Gerdessen; Wopke van der Werf; Anneleen Kuijsten; Sander de Leeuw; Wen-Feng Cong; Shenggen Fan; Edith J.M. Feskens; Tjeerd Jan Stomph (Global Food Security, 2026)

Molecular mechanisms of ion hydration and gas–water diffusion joint controlled the CO2 hydrate growth - Hu Wenfeng; Sun Xiyue; Cheng Chuanxiao; Wu Xuehong; Zhang Xueling; Wang Fan; Zhu Shiquan; Qi Tian; Xiao Yanqiu; Chen Cong (Fuel, 2026)

NaCl substitution characteristics of Salicornia plant salt and potential application in sturgeon caviar: focus on antibacterial activity and phospholipids oxidation - Weijia Zhang; Lingxin Kong; Jingqi Shen; Yuanhui Zhao; Yujin Li; Shuang Cong; Jian Li; Jinlin Wang; Fan Bai; Peng Xu; Lin Gao; Xinxing Xu (Food Chemistry, 2026)

Efficient algorithms for accurately simulating radiative transfer in binary stochastic mixtures in two dimensions - Cong-Zhang Gao; Jian-Wei Yin; Ying Cai; Xu Liu; Zheng-Feng Fan; Pei Wang; Shao-Ping Zhu (Computer Physics Communications, 2026)

Hierarchical energy management system for ships based on MPC-ECMS with multi-dimensional testing and validation - Ailong Fan; Hao Qiu; Liu Yang; Cong Guan; Hanyou Liu; Xuelong Fan (Ocean Engineering, 2026)

Electrospun novel molecular sieve-MOF composite nanofibers for unprecedented cobalt recovery from aqueous solutions - Cong Yin; Qi Zou; Yuntao Lei; Yuchen Zhang; Sufen Li; Fan Liu; Chenghuang Wang; Yonggang Huo; Xingfu Cai; Guoyuan Yuan (Journal of Water Process Engineering, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

The law of oxidation and exothermic of low-rank coal at critical temperature: Based on the isothermal stage experiment method - Bing Lu; Xun Zhang; Ling Qiao; Cong Ding; Nan Fan; Ge Huang; Fengwei Dai (Fuel, 2026)

Unraveling the flavor evolution mechanism in liquid-smoked rainbow trout through integrated lipidomics and flavoromics - Junpeng Zeng; Nan Meng; Xiaowei Fan; Yu Song; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2026)

A novel Vibrio parahaemolyticus strain JM20210818 causing glass post-larvae disease in Litopenaeus vannamei: Histopathology, antimicrobial resistance, genomic and transcriptomic insights - Cong Wang; Qiuping Wu; Guowei Liao; Shengwei Luo; Xiaodong Li; Qingming Kong; Lanfen Fan (Fish & Shellfish Immunology, 2026)

Subsurface fertilization geometry synergies enhanced grain yield, nitrogen use efficiency and reduced greenhouse gas emissions: A global meta-analysis - Yuewen Huo; Feiyu Ying; Mengyang Zhu; Zhiwei Fan; Prakash Lakshmanan; Fusuo Zhang; Wen-Feng Cong (Field Crops Research, 2026)

Research on the impact of resident behavior on energy consumption during the heating period of ultra-low energy buildings - Ru-Xi Ding; Jia-Ze Dai; Ying-Nan Zhang; Xiao-Ping Wu; Cong-Han Yu; Zhenfa Fan (Energy and Buildings, 2026)

Revealing the overlooking role of polysulfides in sulfide-based denitrification biofilms through mathematical modeling - Yan Yang; Yu Liu; Cong Fan; Huimin Fu; Mohamed S. Mahmoud; Kang Dan; Hongxiang Chai (Bioresource Technology, 2026)

Nutrient comparisons among the three varieties Mercenaria mercenaria with different shell colors - Mei-Jie Yang; Pu Shi; Peng-Peng Hu; Shuang Liang; Yan Zou; Zhi Hu; Cong Zhou; Fan-Yu Meng; Kai Xiao; Tao Zhang; Hao Song (Aquaculture, 2026)

Insecticide resistance monitoring and identification of ryanodine receptor mutations driving diamide resistance in Cnaphalocrocis medinalis - Hong-Shuang Li; Pin-Xuan Lin; Meng-Zhen Wang; Bei-Bei Dong; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2026)

Cyproflanilide, a novel meta-diamide insecticide, overcomes multiple insecticide resistance in Cnaphalocrocis medinalis: Evidence from comparative toxicity assays and genome-edited Drosophila - Wen-Chao Ge; Guang-Hang Chen; Bei-Bei Dong; Hong-Shuang Li; Meng-Zhen Wang; Feng-Xia Yang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Devonian brachiopod palaeobiogeography in the Qamdo Block, Eastern Tibet, China - Li Qiao; Wen-Kun Qie; Wen Guo; Cong-Ying Liu; Jin-Ning Fan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Linking ENSO diversity to runoff predictability in China using nonhomogeneous hidden Markov model - Jian Sun; Lei Yan; Jinxia Sha; Dan Xu; Fan Lu; Qinghua Luan; Yuan Liu; Boyuan Lu; Cong Jiang; Lihua Xiong (Journal of Hydrology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A facile and stable single-system fluorescent sensor array for the quantification and discrimination of nitrofuran antibiotics - Yi-Fan Xia; Xiao-Shan Yu; Si-Tong Wen; Hou-Qun Yuan; Cong-Cong Xu; Lan Yang; Yao-Hong Wang; Hua Yu; Ling-Yi Guo; Guang-Ming Bao (Food Chemistry, 2025)

For cereal bran, rating of antioxidant capacity and screening of xanthine oxidase inhibitor - Ye Lou; Ming Cong Fan; Li Wang; Yan Li; Haifeng Qian (Bioactive Carbohydrates and Dietary Fibre, 2025)

A Comparitive Review of the Potato Industries in China and India - Xiao-ye Hu; Huang-zhen Lv; Cong-tao Ren; Fan-kui Zeng (Potato Research, 2025)

Plasma-activated water: A novel approach to modulating main pectin, hemicellulose and cellulose metabolism in goji berry cell walls - Kai-Ping Cong; Ting-Ting Li; Cai-E. Wu; Gong-Jian Fan; Dan-Dan Zhou; Xiao-Jing Li; An-Di Suo (Postharvest Biology and Technology, 2025)

Numerical simulation study on high temporal resolution variation characteristics of atmospheric limb infrared radiation under aurora disturbance - Fan Wu; Congming Dai; Cong Zhang; Wentao Lian; Shunping Chen; Heli Wei (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Alkali-induced Dendrobium officinale polysaccharide-hemp seed protein gels: Insight into structure, molecular interaction mechanisms, and potential as dysphagia food - Tingting Ding; Bei Fan; Xin Xu; Caiyue Chen; Cong Lu; Jiameng Liu; Fengzhong Wang; Jing Sun (Carbohydrate Polymers, 2025)

Novel arneomas A-B and other naphthoquinone active components in Arnebia euchroma I. M. Johnst - Li-Li Han; Yibanuer Reheman; Reyilanmu Maisaidi; Cong-Zhao Fan; Lei-Ling Shi; Sheng-Jie Jia (Natural Product Research, 2025)

Structures and antitumor activities of Arnegutones A–C: A study of three novel active components extracted from Arnebia euchroma - Li-Li Han; Guang-Jie Pan; Si-Qi Li; Yibanuer Reheman; Cong-Zhao Fan; Lei-Ling Shi; Sheng-Jie Jia (Phytochemistry Letters, 2025)

The climate-driven mechanisms of sedimentary evolution in the mud area southwest off Cheju Island during the Holocene - Jingyi Cong; Huisong Fan; Shipu Bi; Xi Mei; Yanguang Dou; Zhonglei Wang; Ze Ning; Yong Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Synergistic charge separation and magnetic recovery in a noble-metal-free Fe3O4/TiO2/Bi photocatalyst for bromate reduction - Ying Xu; Shuili Yu; Zhiqiang Fan; Xingli Ji; Cong Huang; Zheng Xu; Rui Liu; Chao Jiang (Journal of Water Process Engineering, 2025)

Vertical flow structures in a finite patch of natural submerged vegetation under wave-current conditions: Laboratory experiments - Jiadong Fan; Cuiping Kuang; Hongyi Li; Xin Cong; Deping Cao; Rufu Qin (Journal of Hydrology, 2025)

Bismuth nanospheres enabling sacrificial-agent-free bromate photoreduction and total bromine mitigation for safer water treatment - Ying Xu; Shuili Yu; Zhiqiang Fan; Cong Huang; Lei Li; Rui Liu; Zheng Xu (Journal of Hazardous Materials, 2025)

Effect of H2O physicochemical properties on NO formation mechanism in NH3 oxy-steam combustion under MILD mode - Xiaojian Zha; Zewu Zhang; Zhenghong Zhao; Long Yang; Wenchao Mao; Fan Wu; Xiaoshan Li; Cong Luo; Liqi Zhang (Fuel, 2025)

Revisiting the role of solution aggregation in CO₂ desorption: Insights of mass transfer and energy consumption in phase-change absorbents - Bin Xu; Xiaoyi Gao; Wufeng Jiang; Xi Tang; Xiaoshan Li; Cong Luo; Fan Wu; Liqi Zhang (Chemical Engineering Journal, 2025)

Self-suspending catalysts with Co-N4 sites in conjugated polymers for complete PMS-to-Co(IV)=O conversion to enhance ranitidine degradation - Cong Li; Yue Li; Jian Xiao; Minghao Fan; Lele Qiu; Qian Wang; Mario Berrettoni; Silvia Zamponi; Shuaixia Liu; Longlu Wang (Chemical Engineering Journal, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Novel mass transfer kinetics model for predicting phase separation behavior in CO2 capture with energy-saving biphasic absorbents - Bin Xu; Xiaoyi Gao; Wufeng Jiang; Xi Tang; Xiaoshan Li; Cong Luo; Fan Wu; Liqi Zhang (Journal of Cleaner Production, 2025)

Salting-induced lipid hydrolysis and oxidation in dried squid fillets: A mechanistic link to formaldehyde formation, color browning, and flavor alteration - Junpeng Zeng; Xiaowei Fan; Nan Meng; Yanjun Liu; Yu Song; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Bifunctional CMCS bioswitch: A stimuli-responsive platform neutralizing lambda-cyhalothrin resistance and mitigating ecological risk - Zeyu Wang; Mingxia Liu; Zehua Cheng; Zehao Li; Kexin Zhang; Jing Li; Yifan Zhang; Zihao Fan; Lianrui Cao; Lijiang Chen; Cong Li (Chemical Engineering Journal, 2025)

Dry reforming of methane by La2NiO4 perovskite oxide: Cordierite-ceramic-supporting monolithic catalyst with Cu B-site substitution improving reacting performance - Dingshan Cao; Zhen Qin; Cong Luo; Xiaoshan Li; Zhaowei Shi; Fan Wu; Ying Zheng; Liqi Zhang (Chemical Engineering Journal, 2025)

Self-lubricating and self-repairing epoxy coating enabled by ionic liquid-loaded double-walled Ti3C2Tx@PSF microcapsules - Ao Men; Liangliang Xiong; Cong Cai; Xiaoqiang Fan; Minhao Zhu (Chemical Engineering Journal, 2025)

Piezo/photo-catalytic nano-actuators modulating mechanical force for mechanosensitive anti-tumor immunotherapy - Cong Cong; Xuejiao J. Gao; Fei Ye; Xuwu Zhang; Yuchu He; Zhenhe Ma; Wenkang Tu; Weili Xue; Kelong Fan; Dawei Gao (Chemical Engineering Journal, 2025)

Phase separation prediction modeling and structure-activity relationship of CO2 capture by biphasic amine absorbents based on phase separation load - Xiaoyi Gao; Bin Xu; Wufeng Jiang; Xi Tang; Muyi Li; Fan Wu; Cong Luo; Xiaoshan Li; Liqi Zhang (Chemical Engineering Journal, 2025)

Microstructural evolution of tailoring CaO/CaCO3 composites with alumina particle of varied sizes for thermochemical heat storage - Huizhe Wu; Cong Luo; Penghui Yang; Liqi Zhang; Xiaoshan Li; Fan Wu; Ying Zheng (Chemical Engineering Journal, 2025)

The Adhesion Characteristics of Fouling Organism on Two Kinds of Mesh Coat - Lei Li; Jinmeng Bao; Dagui Liao; Yanan Wei; Cong Yan; Xiaoxu Fan; Shen Lin; Dan Liu; Wei Tian; Yanming Sui; Mei Jiang (Thalassas: An International Journal of Marine Sciences, 2025)

Knockdown of ATF3 Alleviates Ischemic Stroke and Inhibits Ferroptosis via Activating the Keap1/Nrf2/HO- 1 Pathway - Xianghong Liu; Haifengqing Li; Fan Zhang; Cong Zhang; Min Zhou; Qing Liu; Guoyong Zeng (Molecular Neurobiology, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Porous hollow spherical CaO heat carriers for thermochemical energy storage prepared by spray pyrolysis based on a dual-fluid atomization method - Tong Luo; Mingyang Houding; Cong Luo; Yi Zhang; Xiaoshan Li; Fan Wu; Liqi Zhang (Chemical Engineering Journal, 2025)

TdCCA with Dual-Modal Signal Fusion: Degenerated Occipital and Frontal Connectivity of Adult Moyamoya Disease for Early Identification - Yuchen Ran; Yingwei Fan; Shuang Wu; Chao Chen; Yangxi Li; Tianxin Gao; Houdi Zhang; Cong Han; Xiaoying Tang (Translational Stroke Research, 2025)

Preparation, identification and application of lipid-Maillard reaction products during the drying process of squid fillets - Junpeng Zeng; Xiaowei Fan; Yanjun Liu; Yu Song; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Mechanistic insights into the enhancement of storage quality characteristics of fresh goji berry through non-thermal optical treatments (UV-C and IPL) - Tingting Li; Zhicheng Yan; Yafei Li; Xiaohong Kou; Caie Wu; Dongying Xu; Dandan Zhou; Kaiping Cong; Gongjian Fan; Xiaojing Li (Food Chemistry, 2025)

Emerging tumor hypoxia-relieving nanotherapeutics for boosting photodynamic therapy - Fujun Yang; Fei Chen; Shumeng Li; Shuang Wang; Lin Peng; Shishan Deng; Fan Zhang; Udo Jeschke; Yuequan Wang; Cong Luo (Chemical Engineering Journal, 2025)

Contriving molecular configuration to realize a bidirectionally stable quasi-solid polymer electrolyte for high-voltage Li metal batteries - Silin Chen; Shunchao Ma; Yu Zhang; Yanan Li; Yutong Yang; Shuainan Wang; Jianli Cao; Siqi Fan; Liqun Sun; Yulong Liu; Lina Cong; Haiming Xie (Chemical Engineering Journal, 2025)

Uncovering the high-activity origin of sulfur doping in Co3O4 for organic pollutant degradation via peroxymonosulfate activation - Jiahong Pan; Zherui Wang; Jiajia Luo; Liwen Fan; Xinyun Li; Chenyi Wang; Yanqing Cong; Tong Wei; Shi-Wen Lv (Chemical Engineering Journal, 2025)

Bacteria in the Phylum Bacillota Degrade Nicotine Through the Variant of Pyridine and Pyrrolidine Pathway - Xiu-Ming Liu; Xuan Hai; Cong-Jian Li; Yu-Fan Han; Xing Chen; Yu-Jin Fan; Jian Wu; En-Min Zhou; Yuan-Dong Li; Ling-Ling Yang; Yan-Qing Duan; Xiao-Yang Zhi (Current Microbiology, 2025)

Optimization of activation conditions of bacterial spore powder dust suppressant and investigation of dust suppression effect under different incubation stages - Yanyun Zhao; Yongxiang Guo; Xiangming Hu; Yue Feng; Suning Li; Yanli Cong; Xueying Fan (Journal of Environmental Chemical Engineering, 2025)

Perylene Diimide-Based A-D-A-Type Organic Additives for Efficient and Stable Inverted Perovskite Solar Cells - Shaojian Li; Kai Chen; Haiqian Ling; Desheng Li; Weixu Duan; Zedong Lin; Cong Liu; Xiangwen Guo; Liwei Zhou; Fan Wu; Tao Liu; Bingsuo Zou (Chemical Engineering Journal, 2025)

Experimental study of thermal comfort by variable temperature and velocity air supply system in operating room - Bin Zhou; Ang Wang; Hui Ren; Jie Xia; Fan Peng; Shao-Cong Wang; Yi-Chu Wang; Hao-Yi Zhao; Wen-Jie Li; Mei-Lan Tan; Risto Kosonen (Building and Environment, 2025)

Integrative analysis based on CRISPR screen identifies apilimod as a potential therapeutic agent for cisplatin-induced acute kidney injury treatment - Yunpeng Chu; Muyun Wei; Zhongyu Cao; Luan Chen; Jie Tan; Wei Bao; Fan Yang; Yingtian Zhang; Yunxiao Lin; Yutong Zhang; Shiyi Li; Cai Lv; et al. (Science China Life Sciences, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

Preparation and characterization of epoxy vitrimer asphalt based on transesterification dynamic covalent bond system - Zhe Zhao; Cong Qi; Guanyu Li; Yujin Yao; Liang Fan; Dongliang Kuang; Huaxin Chen; Yongchang Wu; Peng Xu (Fuel, 2025)

Long-read sequencing reveals novel genetic polymorphisms in the major histocompatibility complex region and their impacts on the Han Chinese population - Cong Zhou; Tingting Gong; Shuhang Li; Li Jin; Shaohua Fan (Science China Life Sciences, 2025)

Long-term monitoring of chloride deposition and its influencing factors around an island in the East China Sea - Jiannan Jia; Zhiqiang Cui; Yuanbei Li; Cong Liu; Qiang Xu; Xianping Fan (Acta Oceanologica Sinica, 2025)

Minor protopanaxadiol type sapogenins from the alkali hydrolysate of stems-leaves of Panax notoginseng - Cong-Cong Jing; Jing-Min Wang; Pei Wang; Lin Guo; Shu-Min Zhang; Ke Liu; Zhen-Yuan Li; Hua-Ying Fan; Ze-Ping Xie (Natural Product Research, 2025)

Field questionnaire survey on thermal comfort of medical personnel in operating rooms for hospitals in Nanjing - Ang Wang; Shao-Cong Wang; Fan Peng; Jie Xia; Hui Ren; Mei-Lan Tan; Bin Zhou (Energy and Buildings, 2025)

Nomogram for Predicting Long-term Outcomes of Encephaloduroarteriosynangiosis in Toddlers with Moyamoya Disease: a Longitudinal and Cross-sectional Study - Qingbao Guo; Yan-Na Fan; Qian-Nan Wang; Jingjie Li; Cong Han; Zhengxing Zou; Simeng Liu; Xiaopeng Wang; Dan Yu; Fangbin Hao; Gan Gao; Qian Zhang; et al. (Translational Stroke Research, 2025)

Proteomic Profiling and Therapeutic Targeting of Oxidative Stress in Autoimmune Encephalitis - Fan Zhang; Cong Zhang; Wei Sun; Shuhua Xie; Pengcheng Wu; Guoyong Zeng; Xianghong Liu (Journal of Molecular Neuroscience, 2025)

Future projections of the rainfall intensity-duration-frequency curves in Beijing-Tianjin-Hebei urban agglomeration based on NEX-GDDP CMIP6 simulations - Lidong Song; Lei Yan; Fuxin Chai; Fan Lu; Jiaqi Zhai; Qinghua Luan; Qiumei Ma; Cong Jiang; Mengjie Zhang; Jian Sun (Sustainable Cities and Society, 2025)

Insight into the mechanism of Maillard reaction and lipids mutually contribute to the flavor release of squid fillets during the drying process - Junpeng Zeng; Nan Meng; Yu Song; Xiaowei Fan; Xiaoming Jiang; Peixu Cong; Yanjun Liu; Changhu Xue; Jie Xu (Food Chemistry, 2025)

The structure–activity relationship for CO2 absorption heat of chain diamines: Effects of amino types, methyl/ethyl groups, and chain lengths - Xi Tang; Ge Gao; Wufeng Jiang; Bin Xu; Fan Wu; Cong Luo; Xiaoshan Li; Liqi Zhang (Chemical Engineering Journal, 2025)

Optimization and degradation pathway of DEP in water by dielectric barrier discharge - Xinjun Shen; Fan He; Siyu Zhang; Xu Gao; Cong Wang (Process Safety and Environmental Protection, 2025)

Assessment of CO2 fluxes in the hinterland of the Gurbantunggut Desert and its response to climate change - Ali Mamtimin; Gulnur Amar; Yu Wang; Jian Peng; Hajigul Sayit; Jiacheng Gao; Kun Zhang; Meiqi Song; Ailiyaer Aihaiti; Cong Wen; Fan Yang; Wen Huo; et al. (Journal of Environmental Management, 2025)

Virulence expression difference to intestinal cells of different pathogenic Listeria monocytogenes contaminating sausages after simulated digestive tract - Cong Zhou; Yafang Zou; Haorui Huang; Fanwen Zhao; Xia Fan; Li Bai; Xinhao Zhang; Keping Ye (International Journal of Food Microbiology, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Lipid-involved browning mechanism during the drying process of squid - Junpeng Zeng; Yu Song; Xiaowei Fan; Yanjun Liu; Peixu Cong; Xiaoming Jiang; Jie Xu; Changhu Xue (Food Chemistry, 2025)

Mechanism and Models of Nano-Confined Slip Flow of Shale Oil - Ren-Shi Nie; Jing-Shun Li; Jian-Chun Guo; Zhangxin Chen; Jingcheng Liu; Cong Lu; Fan-Hui Zeng (Natural Resources Research, 2025)

Insight into the anti-T2DM effect and mechanism of apricot polysaccharide through the combination of 16S rRNA sequencing and non-target metabolomics - Andi Suo; Gongjian Fan; Caie Wu; Tingting Li; Xiaojing Li; Dandan Zhou; Kaiping Cong; Xin Cheng (Food Bioscience, 2025)

CeO2 enhanced performance of NiFe2O4-CaO for carbon capture and in-situ hydrogenation conversion to CO - Yu Fan; Bowen Lu; Xinyu Zhi; Cong Luo; Liqi Zhang (Journal of Environmental Chemical Engineering, 2024)

Dynamic changes, cycling and downward fate of dissolved carbon and nitrogen photosynthetically-derived from glaciers in upper Indus river basin - Mohd Aadil Bhat; Si-Liang Li; Cong-Qiang Liu; Nicola Senesi; Giorgio S. Senesi; Davide Vione; Daidu Fan; Jie Yuan; Mashura Shammi; Khan M.G. Mostofa (Environmental Research, 2024)

Metallic engineering in metal-porphyrin frameworks for highly efficient CO2 photoreduction - Shu-Cong Fan; Wenyu Yuan; Jia-Wen Wang; Chenchen Xing; Dan Li; Ying Wang; Quan-Guo Zhai (Chemical Engineering Journal, 2024)

A novel variant (p.A524P) in Spastin is responsible for a Chinese family with hereditary spastic paraplegia - Yu-Han Jin; Yang-Ziyu Xiang; Mei-Fang Zhao; Yi-Hui Liu; Liang-Liang Fan; Xiao-Cong Li (Molecular Biology Reports, 2024)

LncRNA018392 promotes the proliferation of Liaoning cashmere goat skin fibroblasts by upregulating CSF1R through binding to SPI1 - Mei Jin; Weiyu Fan; Suhe Lv; Tianwei Xue; Linlin Cong; Xinyang Liu; Lixin Cui (Molecular Biology Reports, 2024)

Energy deprivation-induced autophagy and aggrephagy: insights from yeast and mammals - Siyu Fan; Yingcong Chen; Weijing Yao; Cong Yi (Journal of Zhejiang University-SCIENCE B, 2024)

The Key Phytochemical Cue Camphor Is a Promising Lure for Traps Monitoring the New Monophagous Camphor Tree Borer Pagiophloeus tsushimanus (Coleoptera: Curculionidae) - Cong Chen; Tian Xu; Shouyin Li; Mingyu Xue; Yadi Deng; Binqi Fan; Chufeng Yang; Dejun Hao (Journal of Chemical Ecology, 2024)

A novel process for producing Al-Si alloy utilizing aluminum-silicon oxide extracted from coal fly ash - Zhiwei Liu; Minghui Guo; Hongkun Niu; Cong Wang; Chao Fan; Bingliang Gao (Process Safety and Environmental Protection, 2024)

Area-wide survey and monitoring of insecticide resistance in the brown planthopper, Nilaparvata lugens (Stål), from 2020 to 2023 in China - Wen-Nan Ye; Yu Li; Yan-Chao Zhang; Zhao-Yu Liu; Xin-Yu Song; Xin-Guo Pei; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2024)

Vertical flow structures on a vegetated immobile bed under wave-current conditions: Laboratory experiments - Jiadong Fan; Cuiping Kuang; Hongyi Li; Xin Cong; Wei Xing; Jilong Chen (Ocean Engineering, 2024)

Effects of cutting temperature on the genes and fatigue properties of asphalt during its refining process - Guanyu Li; Cong Qi; Shanjian Han; Liang Fan; Dongliang Kuang; Huanxin Chen; Yongchang Wu (Fuel, 2024)

Additive patterns in near-infrared diffuse reflectance spectra: Implications for product formulation and analysis - Le Zhao; Youyan Liang; Nuohan Zhang; Yanbin Chang; Meijuan Fan; Cong Wang; Beibei Li; Hongbo Wang; Yu Liu; Hongxiao Yu; Song Yang; Fuwei Xie; et al. (Food Control, 2024)

An in-depth review of the dermal toxicity of T-2 toxin: Clinical symptoms, injury mechanisms, and treatment approach - Jiayan Fan; Wenxi Song; Youshuang Wang; Shuo Li; Cong Zhang; Xuebing Wang; Xu Yang (Food and Chemical Toxicology, 2024)

New insights into the functional group influence on CO2 absorption heat and CO2 equilibrium solubility by piperazine derivatives - Xi Tang; Bin Xu; Wufeng Jiang; Xiaoshan Li; Ge Gao; Fan Wu; Cong Luo; Liqi Zhang (Chemical Engineering Journal, 2024)

A phase separation prediction model for CO2 capture by biphasic amine absorbents - Xiaoyi Gao; Wufeng Jiang; Bin Xu; Yongsheng Fan; Cong Luo; Fan Wu; Xiaoshan Li; Liqi Zhang (Chemical Engineering Journal, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Personalized air curtain optimized to reduce fine particle exposure in industrial environments with different indoor airflow conditions - Jianchao Ma; Hua Qian; Fan Liu; Cong Liu; Xiaohong Zheng; Fujiang Chen (Building and Environment, 2024)

VCAT: an integrated variant function annotation tools - Bi Huang; Cong Fan; Ken Chen; Jiahua Rao; Peihua Ou; Chong Tian; Yuedong Yang; David N. Cooper; Huiying Zhao (Human Genetics, 2024)

Transcriptional RNA sequencing reveals the molecular mechanism of dielectric barrier discharge cold plasma against postharvest pathogen Alternaria alternata - Tingting Li; Xiaodong Chen; Jinfeng Cheng; Zhicheng Yan; Caie Wu; Dandan Zhou; Gongjian Fan; Xiaojing Li; Kaiping Cong; Xu Li (Food Bioscience, 2024)

Unlocking the ultrafast laser response and low initiation energy of perchlorate-free tetrazine-based energetic coordination compounds - Hong-Yi Bian; Yun-Fan Yan; Meng Cui; Hao-Hui Xie; Tian-Tian Song; Xiao-Di Guo; Jian-Gang Xu; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2024)

Multi-dimensional signals coupling of simultaneous acquisition stripping current with laser-induced breakdown spectroscopy for accurate analysis of Cd(II) in coexisting Cu(II) - Yuan-Fan Yang; Zong-Yin Song; Zi-Hao Liu; Zhi-Wei Gao; Xin Cai; Cong-Cong Huang; Pang-Da Dai; Meng Yang; Pei-Hua Li; Shi-Hua Chen; Xing-Jiu Huang (Analytica Chimica Acta, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Numerical investigation on the vertical jet fire impinging on the horizontal cylindrical obstacle in a ship engine room: Characteristics and new prediction models of flame length - Shaogang Zhang; Yongqiang Fan; Long Shi; Jiahao Liu; Jianghong Liu; Jinhui Wang; Beihua Cong (Ocean Engineering, 2024)

A bioinspired polymer composite with tough, fatigue-resistant adhesion, and high interfacial thermal conductance via interfacial crosslinking - Xiangliang Zeng; Jianfeng Fan; Xiaoliang Zeng; Cong Yang; Xinnian Xia (Chemical Engineering Journal, 2024)

Characterization of two virulent Salmonella phages and transient application in egg, meat and lettuce safety - XiaoWen Sun; Fan Xue; Cong Cong; Bilal Murtaza; LiLi Wang; XiaoYu Li; ShuYing Li; YongPing Xu (Food Research International, 2024)

An ionic liquid-modified PEDOT/Ti3C2TX based molecularly imprinted electrochemical sensor for pico-molar sensitive detection of L-Tryptophan in milk - Cong Xue; Ruxangul Jamal; Tursun Abdiryim; Xiong Liu; Fangfei Liu; Feng Xu; Qian Cheng; Xinsheng Tang; Nana Fan (Food Chemistry, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Genetic association of lipid traits and lipid-related drug targets with normal tension glaucoma: a Mendelian randomization study for predictive preventive and personalized medicine - Tianyi Kang; Yi Zhou; Cong Fan; Yue Zhang; Yu Yang; Jian Jiang (EPMA Journal, 2024)

Characterization of oxylipins in Antarctic krill oil (Euphausia superba) during storage based on RPLC–MS/MS analysis - Nan Meng; Xincen Wang; Yu Song; Xiaowei Fan; Junpeng Zeng; Tingyu Feng; Peixu Cong; Jie Xu; Changhu Xue (Food Chemistry, 2024)

Water effect on CO2 absorption mechanism and phase change behavior in [N1111][Gly]/EtOH anhydrous biphasic absorbent: In density functional theory and molecular dynamics view - Wufeng Jiang; Ge Gao; Xiaoyi Gao; Bin Xu; Fan Wu; Xiaoshan Li; Liqi Zhang; Cong Luo (Chemical Engineering Journal, 2024)

Transforming crystal structures of cobalt molybdate to generate electron-rich sites for electrochemical detection of Pb(II) - Yang-Zhi Liu; Xin Cai; Cong-Cong Huang; Zi-Hao Liu; Yuan-Fan Yang; Yong-Yu Li; Meng Yang; Shi-Hua Chen; Xing-Jiu Huang (Analytica Chimica Acta, 2024)

The G932C mutation of chitin synthase 1 gene (CHS1) mediates buprofezin resistance as confirmed by CRISPR/Cas9-mediated knock-in approach in the brown planthopper, Nilaparvata lugens - Fan Zhang; Yan-Chao Zhang; Zhi-Tao Yu; Bing Zeng; Hao Sun; Yu-Qiu Xie; Kun Yan Zhu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2024)

High-efficiency removal of ciprofloxacin by persulfate activated with 3D Bi2WO6/g-C3N4/GA Z-scheme heterojunction under simulated sunlight - Yukun Li; Haiyang Zhang; Sen Yao; Cong Chao; Qishi Chen; Junhua Chen; Fengjuan Fan; Hongyuan Jia; Mingjia Dong (Journal of Water Process Engineering, 2024)

A simple strategy for d/l-carnitine analysis in food samples using ion mobility spectrometry and theoretical calculations - Cong Liu; Ying Zou; Manli Zhang; Chaoxian Chi; Di Zhang; Fangling Wu; Chuan-Fan Ding (Food Chemistry, 2024)

A fluorescent aptasensor for enzyme-free and sensitive detection of kanamycin based on entropy-driven strand displacement reaction - Longjie Xie; Cong Fan; Yang Liu; Qin Chen; Xian Chen (Analytica Chimica Acta, 2024)

Strain-specific responses of Penaeus vannamei to two Enterococcus faecium strains supplementation: A trade-off between growth and immunity - Kai Luo; Shishuang Wang; Yang Liu; Guangcai Qin; Yumeng Xie; Cong Wei; Zeyang Guo; Ruiyong Fan; Xiangli Tian (Aquaculture, 2024)

Exploring the ecological meanings of temperature sensitivity of ecosystem respiration from different methods - Yang Zhang; Gaofeng Zhu; Kun Zhang; Heng Huang; Liyang He; Cong Xu; Huiling Chen; Yonghong Su; Yuzhong Zhang; Haochen Fan; Boyuan Wang (Science of The Total Environment, 2024)

Research on aquatic microcosm: Bibliometric analysis, toxicity comparison and model prediction - Fan Wu; Zhengtao Liu; Jiaqi Wang; Xusheng Wang; Cong Zhang; Shunhao Ai; Ji Li; Xiaonan Wang (Journal of Hazardous Materials, 2024)

Energy partitioning over an irrigated vineyard in arid northwest China: Variation characteristics, influence degree, and path of influencing factors - Huiling Chen; Yongtai Zhu; Gaofeng Zhu; Yang Zhang; Liyang He; Cong Xu; Kun Zhang; Jing Wang; Ramamoorthy Ayyamperumal; Haochen Fan; Boyuan Wang (Agricultural and Forest Meteorology, 2024)

Occurrence, distribution, and risk assessment of antibiotics in a typical aquaculture area around the Dongzhai Harbor mangrove forest on Hainan Island - Tuan-Tuan Wang; Shuai Shao; Shi-Di Fan; Wang-Qing Tang; Jiang-Wei Miao; Sai Wang; Xiao-Cong Cao; Chuan Liu; Guang-Guo Ying; Zhong-Bing Chen; Hai-Long Zhou; Xiao-Ping Diao; et al. (Science of The Total Environment, 2024)

Plasma-activated water regulates water distribution to resist softening of goji berries - Kai-Ping Cong; Cai-E. Wu; Ting-Ting Li; Gong-Jian Fan; Dan-dan Zhou; Xiao-jing Li; An-Di Suo; Xu Li (Postharvest Biology and Technology, 2024)

Hydrodynamic influences on water exchange capacity of a coastal lagoon after phasic restoration projects - Jiadong Fan; Cuiping Kuang; Xin Cong; Lixin Gong; Gang Wang; Rongrong Xing (Estuarine, Coastal and Shelf Science, 2024)

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

Paeoniflorin alleviated muscle atrophy in cancer cachexia through inhibiting TLR4/NF-κB signaling and activating AKT/mTOR signaling - Zixia Zhu; Cong Li; Xiaofan Gu; Xiaoting Wang; Gang Zhang; Meng Fan; Yun Zhao; Xuan Liu; Xiongwen Zhang (Toxicology and Applied Pharmacology, 2024)

Plastic food? Energy compensation of zebrafish (Danio rerio) after long-term exposure to polylactic acid biomicroplastics - Zhenghua Duan; Yizhuo Chen; Yuhang Dou; Huiyu Fan; Jing Wang; Jiaoyue Cong; Hongwen Sun; Lei Wang (Journal of Hazardous Materials, 2024)

Effects of irrigation and nitrogen levels on yield and water-nitrogen-radiation use efficiency of drip-fertigated cotton in south Xinjiang of China - Zhentao Bai; Cong Xie; Jiang Yu; Wenqiang Bai; Shengzhao Pei; Yunxia Li; Zhijun Li; Fucang Zhang; Junliang Fan; Feihu Yin (Field Crops Research, 2024)

Hierarchical NiCoP/NiCo architecture on Ni mesh boosts hydrogen production under industrial alkaline conditions - Cong Chen; Ju Zhou; Junxia Shen; Tai An; Zhihe Wei; Yazhou Zhang; Sheng Ju; Yang Peng; Ronglei Fan; Mingrong Shen (Chemical Engineering Journal, 2024)

Population dynamics of a stoichiometric aquatic tri-trophic level model with fear effect - Pingping Cong; Meng Fan; Xingfu Zou (Mathematical Biosciences, 2024)

Dry reforming of methane by La2NiO4 perovskite oxide: B-site substitution improving reactivity and stability - Dingshan Cao; Cong Luo; Tong Luo; Zhaowei Shi; Fan Wu; Xiaoshan Li; Ying Zheng; Liqi Zhang (Chemical Engineering Journal, 2024)

Microbial response and spatial profiling of nitrite-producing denitrification granular sludge in-situ exposed to high nitrite stress - Jiarui Fan; Rui Du; Qingtao Liu; Cong Li; Yongzhen Peng (Chemical Engineering Journal, 2024)

Engineering photo-methylotrophic Methylobacterium for enhanced 3-hydroxypropionic acid production during non-growth stage fermentation - Zeng-Xin Ma; Chen-Xi Feng; Ya-Zhen Song; Jing Sun; Yi Shao; Shu-Zhen Song; Bin Wan; Cong Zhang; Huan Fan; Kai Bao; Song Yang (Bioresource Technology, 2024)

Oxidation potential of PM2.5 in a mechanical processing plant and its association with metal composition - Jianchao Ma; Cong Liu; Fan Liu; Xiaohong Zheng; Hua Qian (Atmospheric Environment, 2024)

Novel fluorescence nano-orbital biosensor for highly sensitive microRNA detection - Cong Fan; Longjie Xie; Feng Zhao; Jingjing Wang; Xiandong Lin; Xian Chen (Analytica Chimica Acta, 2024)

Endophytic bacteria from diseased plant leaves as potential biocontrol agents of cucumber Fusarium wilt - Yinqing Tan; Changxia Du; Li Xu; Cong Yue; Xingchen Liu; Huaifu Fan (Journal of Plant Pathology, 2024)

Reaction behaviors in pulverized coal MILD-oxy combustion affected by physical and chemical effects of diluents - Zhenghong Zhao; Zewu Zhang; Xiaojian Zha; Ge Gao; Fan Wu; Xiaoshan Li; Cong Luo; Liqi Zhang (Fuel, 2024)

Expansive microbial metabolic versatility and spatial biodiversity of anammox coupling with denitrification granular sludge under different feeding strategies - Cong Li; Rui Du; Qingtao Liu; Jiarui Fan; Yongzhen Peng (Chemical Engineering Journal, 2024)

Farmers perceive diminishing ecosystem services, but overlook dis-services in intensively used agricultural landscapes in the North China Plain - Jiali Cheng; Zhan Xu; Zhengyuan Liang; Fan Li; Wen-Feng Cong; Chaochun Zhang; Lei Song; Chong Wang; Fusuo Zhang; Andries Richter; Wopke van der Werf; Jeroen C.J. Groot (Journal of Environmental Management, 2023)

Interplay of shell evolution and oxidation depth on the ignition and combustion behavior of aluminum nanoparticles - Yiming Lu; Lili Ye; Fan Wang; Lei Zhang; Yubo Bi; Haiyong Cong; Mingshu Bi (Fuel, 2023)

Influence of plasma-activated γ-aminobutyric acid on tissue browning and water migration in fresh-cut potato during storage - Dandan Zhou; Tian Yang; Qiang Liu; Xiaodong Chen; Kaiping Cong; Tingting Li; Caie Wu; Gongjian Fan; Bariami Wafae; Xiaojing Li (Food Bioscience, 2023)

Constructing and Validating a Network of Potential Olfactory Sheathing Cell Transplants Regulating Spinal Cord Injury Progression - Yan Zhang; Yu-shen Yang; Wei-can Chen; Cong-mei Wang; He-fan He (Molecular Neurobiology, 2023)

Fagus diversification in China in relation to East Asian monsoon evolution - Qiuchi Wan; Kangyou Huang; Su-Fang Chen; Frédéric Boyer; Pierre Taberlet; Hongwei Li; Cong Chen; Yongjie Tang; Zhuo Zheng; Xiao Zhang; Rachid Cheddadi; Qiang Fan (Quaternary Science Reviews, 2023)

Reverse genetic study reveals the molecular targets of chordotonal organ TRPV channel modulators - Yu-Xuan Peng; Zhao-Yu Liu; Pin-Xuan Lin; Shao-Cong Su; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2023)

Systemic subchronic toxicity and comparison of four selenium nutritional supplements by 90-day oral exposure in Sprague-Dawley rats - Lu Yu; Yanmei Li; Wen Qu; Yanhua Zheng; Xuejiao Chen; Shaohua Fu; Jingjing Qu; Jie Tian; Shuiyuan Cheng; Xin Cong; Bolin Fan; Chunhong Wang (Food and Chemical Toxicology, 2023)

NCBP1 Improves Cognitive Function in Mice by Reducing Oxidative Stress, Neuronal Loss, and Glial Activation After Status Epilepticus - Xiaoying Gao; Zhipeng You; Cong Huang; Zhixiong Liu; Zixiao Tan; Jiran Li; Yang Liu; Xingan Liu; Fan Wei; Zhijie Fan; Sihua Qi; Jiahang Sun (Molecular Neurobiology, 2023)

The evolution of insecticide resistance in the white backed planthopper Sogatella furcifera (Horvath) of China in the period 2014–2022 - Ya-Ting Liu; Xin-Yu Song; Bin Zeng; Wen-Jing Zhang; Xing-Yu Chen; Ze-Rui Feng; Hua-Yang Yu; Cong-Fen Gao; Shun-Fan Wu (Crop Protection, 2023)

Carbon deposition properties and regeneration performance of La2NiO4 perovskite oxide for dry reforming of methane - Dingshan Cao; Cong Luo; Zengqiang Tan; Tong Luo; Zhaowei Shi; Fan Wu; Xiaoshan Li; Ying Zheng; Liqi Zhang (Journal of Environmental Chemical Engineering, 2023)

New insights into the structure-activity relationship for CO2 capture by tertiary amines from the experimental and quantum chemical calculation perspectives - Ge Gao; Bin Xu; Xiaoyi Gao; Wufeng Jiang; Zhenghong Zhao; Xiaoshan Li; Cong Luo; Fan Wu; Liqi Zhang (Chemical Engineering Journal, 2023)

Carbon-coating small-molecule organic bipolar electrodes for symmetric Li-dual-ion batteries - Chenbin Tang; Bangshuai Wei; Wu Tang; Yan Hong; Meichen Guo; Xuesong He; Jiahui Hu; Shan Jia; Cong Fan (Chemical Engineering Journal, 2023)

Green extraction of carotenoids from apricot flesh by ultrasound assisted corn oil extraction: Optimization, identification, and application - Andi Suo; Gongjian Fan; Caie Wu; Tingting Li; Kaiping Cong (Food Chemistry, 2023)

Copper Azide-based Complexes without Repulsive Steric Clashes between Azides for Advanced Primary Explosives - Yun-Fan Yan; Qian-You Wang; Meng Cui; Hong-Yi Bian; Yong-Fang Han; Jian-Gang Xu; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2023)

Mechanism changing iron solubility and oxidative potential associated with PM2.5 during outdoor-to-indoor transport - Hao Hu; Cong Liu; Fan Yang; Hua Qian; Armistead Russell; Abbas Shahsavani; Haidong Kan (Atmospheric Environment, 2023)

Activation of Cannabinoid Receptor 1 in GABAergic Neurons in the Rostral Anterior Insular Cortex Contributes to the Analgesia Following Common Peroneal Nerve Ligation - Ming Zhang; Cong Li; Qian Xue; Chang-Bo Lu; Huan Zhao; Fan-Cheng Meng; Ying Zhang; Sheng-Xi Wu; Yan Zhang; Hui Xu (Neuroscience Bulletin, 2023)
The rostral agranular insular cortex (RAIC) has been associated with pain modulation. Although the endogenous cannabinoid system (eCB) has been shown to regulate chronic pain, the roles of eCBs in the RAIC remain elusive under the neuropathic pain state. Neuropathic pain was induced in C57BL/6 mice by common peroneal nerve (CPN) ligation. The roles of the eCB were tested in the RAIC of ligated CPN C57BL/6J mice, glutamatergic, or GABAergic neuron cannabinoid receptor 1 (CB1R) knockdown mice with the whole-cell patch-clamp and pain behavioral methods. The E/I ratio (amplitude ratio between mEPSCs and mIPSCs) was significantly increased in layer V pyramidal neurons of the RAIC in CPN-ligated mice. Depolarization-induced suppression of inhibition but not depolarization-induced suppression of excitation in RAIC layer V pyramidal neurons were significantly increased in CPN-ligated mice. The analgesic effect of ACEA (a CB1R agonist) was alleviated along with bilateral dorsolateral funiculus lesions, with the administration of AM251 (a CB1R antagonist), and in CB1R knockdown mice in GABAergic neurons, but not glutamatergic neurons of the RAIC. Our results suggest that CB1R activation reinforces the function of the descending pain inhibitory pathway via reducing the inhibition of glutamatergic layer V neurons by GABAergic neurons in the RAIC to induce an analgesic effect in neuropathic pain.

Correction: Effects of Pharmacological Intervention on Recovery After Sevoflurane Anesthesia in Children: A Network Meta-analysis of Randomized Controlled Trials - Cong-mei Wang; Yan Zhang; Wei-can Chen; Shu Lin; He-fan He (Molecular Neurobiology, 2023)

The role of social impact on consumer attitudes toward green and healthy home appliances during the COVID-19 pandemic - Jun Fan; Lijuan Peng; Tinggui Chen; Guodong Cong (Environment, Development and Sustainability, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Evaluation of sludge anaerobic fermentation driving partial denitrification capability: In view of kinetics and metagenomic mechanisms - Qingtao Liu; Cong Li; Jiarui Fan; Yongzhen Peng; Rui Du (Science of The Total Environment, 2023)

Effects of Pharmacological Intervention on Recovery After Sevoflurane Anesthesia in Children: a Network Meta-analysis of Randomized Controlled Trials - Cong-mei Wang; Yan Zhang; Wei-can Chen; Shu Lin; He-fan He (Molecular Neurobiology, 2023)

Indoxyl sulfate in atherosclerosis - Cong Lu; Li Wu; Mu-Yao Tang; Yi-Fan Liu; Lei Liu; Xi-Ya Liu; Chun Zhang; Liang Huang (Toxicology Letters, 2023)

A new method for long-term in situ monitoring of seabed interface evolution: A self-potential probe - Zhihan Fan; Xianming Zhu; Haibo Xu; Zhiwen Sun; Hong Zhang; Xianbin Bi; Cong Hu; Dequan Lu; Zhongqiang Sun; Kai Li; Yongzheng Quan; Yonggang Jia (Ocean Engineering, 2023)

Molecular weight determination of low molecular weight hyaluronic acid and chondroitin sulfate by gel permeation chromatography - Zhiqing Tian; Fan Jiang; Haolong Cong; Shuifang Zhu (Carbohydrate Polymers, 2023)

Bone marrow mesenchymal stem cell-derived exosomes loaded with miR-26a through the novel immunomodulatory peptide DP7-C can promote osteogenesis - Shuang Lai; Li Deng; Cong Liu; Xinlun Li; Liyuan Fan; Yushu Zhu; Yiling Yang; Yandong Mu (Biotechnology Letters, 2023)

Nutrient composition, functional activity and industrial applications of quinoa (Chenopodium quinoa Willd.) - Guixing Ren; Cong Teng; Xin Fan; Shengyuan Guo; Gang Zhao; Lizhen Zhang; Zou Liang; Peiyou Qin (Food Chemistry, 2023)

Vacancy-clusters in-situ induced via microwave-irradiation enable high-durability and capacitor-level rate li-ion storage - Tingting Zhao; Cong Liu; Tao Meng; Fenyun Yi; Aimei Gao; Fan Zhang; Dong Shu; Yexiang Tong (Chemical Engineering Journal, 2023)

Investigating food web structure and system function of an artificial reef ecosystem based on carbon and nitrogen stable isotope analysis: implications for reef management - Jie Feng; Xiaolong Zhao; Fan Bi; Wei Zhao; Liang Zhao; Hao Song; Meijie Yang; Zhi Hu; Cong Zhou; Pu Shi; Pengpeng Hu; Peizhen Ma; et al. (Frontiers in Marine Science, 2023)
Introduction Food web is an important basis for identifying trophodynamic processes, and evaluating the structural and functional characteristics of ecosystems. The trophodynamics and system function of artificial reef (AR) ecosystems have rarely been examined. Methods Stable isotope analysis was used to investigate the food web structure and functions of an artificial reef (AR) ecosystem in this study. Results and Discussion The δ13C and δ15N values of particulate organic matter (POM) in AR showed noticeable seasonal changes, and the δ13C value of POM in autumn was significantly higher than that in other seasons (p<0.05). There were no significant seasonal variations in the δ13C values of solid organic matter (SOM), and no significant difference between SOM and POM was observed except in autumn. Moreover, macroalgae did not significantly affect the δ13C values of SOM. Phytoplankton may be the primary nutrient source in the AR ecosystem. The δ13C values of most crustaceans in the AR were approximately between (-17.03 ± 0.22) ‰ – (-17.74 ± 0.07) ‰, higher than those of most fish, indicating that they may have different basal nutrient sources. The trophic level (TL) of invertebrates was between 2.00 and 3.09, and that of fish was between 2.98 and 3.66. The distribution of δ13C and TLs of crustaceans and fish showed that, except for crustaceans, bivalve shellfish and zooplankton might also be important food sources for fish in the AR ecosystem. Conclusion The δ13C and δ15N values of most species in the AR showed good continuity, indicating that they may be mainly produced from the AR ecosystem. Migratory species such as Lateolabrax japonicus and Sepiella maindroni showed higher δ13C values, indicating that they may have migrated from other sea areas. To maintain the stability of the ecosystem structure and function of the AR ecosystem, fishing activities should be carried out following the maximum sustainable yield theory. Future research needs to identify the nutritional relationship between AR and its adjacent sea areas, to depict the food web structure of the AR with higher accuracy.

Global, regional, and national burden of preterm birth attributable to ambient and household PM2.5 from 1990 to 2019: Worsening or improving? - Xiao-Xuan Liu; Shu-Jun Fan; Ya-Na Luo; Li-Xin Hu; Cong-Cong Li; Yi-Dan Zhang; Jia-Xin Li; Hui-Ling Qiu; Guang-Hui Dong; Bo-Yi Yang (Science of The Total Environment, 2023)

Combustion behaviors of pulverized coal MILD-oxy combustion under different steam injection parameters - Zhenghong Zhao; Zewu Zhang; Xiaojian Zha; Ge Gao; Xiaoshan Li; Fan Wu; Cong Luo; Liqi Zhang (Fuel, 2023)

Supplementation of quinoa peptides alleviates colorectal cancer and restores gut microbiota in AOM/DSS-treated mice - Xin Fan; Huimin Guo; Cong Teng; Xiushi Yang; Peiyou Qin; Aurore Richel; Lizhen Zhang; Christophe Blecker; Guixing Ren (Food Chemistry, 2023)

Development and challenges of deep eutectic solvents for cathode recycling of end-of-life lithium-ion batteries - Yuxin Fan; Yuelin Kong; Pinxian Jiang; Guohua Zhang; Jianlong Cong; Xinyue Shi; Yukun Liu; Ping Zhang; Renyuan Zhang; Yunhui Huang (Chemical Engineering Journal, 2023)

A new chloro-azaphilone derivative with pro-angiogenesis activity from the hadal trench-derived fungus Chaetomium globosum YP-106 - Yaqin Fan; Chunjiao Jiang; Peihai Li; Cong Wang; Hao Chen (Journal of Oceanology and Limnology, 2023)

Fe(II)-mediated transformation of schwertmannite associated with calcium from acid mine drainage treatment - Cong Fan; Chuling Guo; Wei Chen; Guining Lu; Yu Shen; Zhi Dang (Journal of Environmental Sciences, 2023)

Enhancement of organics and nutrient removal and microbial mechanism in vertical flow constructed wetland under a static magnetic field - Cong Li; Likui Feng; Jianjun Lian; Xiaoting Yu; Chunzhen Fan; Zhen Hu; Haiming Wu (Journal of Environmental Management, 2023)

Characterization of bioactives and in vitro biological activity from Protaetia brevitarsis larval extracts obtained by different pretreatment extractions - Zong-Qi Zhang; Si-Cong Chen; Xun-Fan Wei; Jin Geng; Zhuo-Xiao Sui; Qing-Lei Wang; Chun-Qin Liu; Jin-Hua Xiao; Da-Wei Huang (Food Chemistry, 2023)

Carbon isotope of the Early Cretaceous sediments from the West Pacific and the Sulu orogenic belt: Implying the global atmospheric pCO2 changes during the Early Aptian Oceanic Anoxic Event 1a - Si-fan Wu; Cong-ying Li; Jing Huang (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Stress sensitivity of coal reservoir and its impact on coalbed methane production in the southern Qinshui Basin, north China - Huimin Jia; Yidong Cai; Qiujia Hu; Cong Zhang; Feng Qiu; Bin Fan; Chonghao Mao (Frontiers of Earth Science, 2023)

Pulsed light improved the shelf life of apricot （after simulated long-distance air transportation） by regulating cell wall metabolism - Xiaowen Hua; Tingting Li; Caie Wu; Dandan Zhou; Gongjian Fan; Xiaojing Li; Kaiping Cong; Zhicheng Yan; Xin Cheng (Postharvest Biology and Technology, 2023)

Experimental and kinetic study on the catalytic effect of AAEMs on coal char combustion under O2/CO2 atmospheres - Xiaojian Zha; Zewu Zhang; Zhenghong Zhao; Xiaoshan Li; Cong Luo; Fan Wu; Liqi Zhang (Fuel, 2023)

Effect of ionic radius and valence state of alkali and alkaline earth metals on promoting the catalytic performance of La2O3 catalysts for glycerol carbonate production - Jialin Yu; Ke Wang; Shibo Shao; Wei Li; Shangfeng Du; Xianfeng Chen; Cong Chao; Xianfeng Fan (Chemical Engineering Journal, 2023)

Metagenomics-based interpretation of selective bioaugmentation promoting partial-denitrification coupling with anammox process reactivation in suspended sludge system - Cong Li; Qingtao Liu; Jiarui Fan; Yongzhen Peng; Rui Du (Chemical Engineering Journal, 2023)

Emission and oxidative potential of PM2.5 generated by nine indoor sources - Hao Hu; Jin Ye; Cong Liu; Lan Yan; Fan Yang; Hua Qian (Building and Environment, 2023)

Piceatannol enhances Beclin-1 activity to suppress tumor progression and its combination therapy strategy with everolimus in gastric cancer - Longtao Huangfu; Xiaoyang Wang; Shanshan Tian; Junbing Chen; Xueying Wang; Biao Fan; Qian Yao; Gangjian Wang; Cong Chen; Jing Han; Xiaofang Xing; Jiafu Ji (Science China Life Sciences, 2023)

Profiling human pathogenic repeat expansion regions by synergistic and multi-level impacts on molecular connections - Cong Fan; Ken Chen; Yukai Wang; Edward V. Ball; Peter D. Stenson; Matthew Mort; Albino Bacolla; Hildegard Kehrer-Sawatzki; John A. Tainer; David N. Cooper; Huiying Zhao (Human Genetics, 2023)

Rock characteristics and dynamic fragmentation process of the 2018 Daanshan rockslide in Beijing, China - Tian-zhen Fan; Hui-cong An; Chao-jun Ouyang; Dong-po Wang (Journal of Mountain Science, 2023)

Description of a moderately acidotolerant and aerotolerant anaerobic bacterium Acidilutibacter cellobiosedens gen. nov., sp. nov. within the family Acidilutibacteraceae fam. nov., and proposal of Sporanaerobacteraceae fam. nov. and Tepidimicrobiaceae fam. nov. - Hui Fan; Jiang Li; Weidong Wu; Rui Chen; Min Yang; Yinggang Zhang; Lulu Cong; Lirong Dai; Yu Deng; Lei Cheng; Shichun Ma (Systematic and Applied Microbiology, 2023)

Knockout of the odorant receptor co-receptor, orco, impairs feeding, mating and egg-laying behavior in the fall armyworm Spodoptera frugiperda - Hao Sun; Ling-Ao Bu; Shao-Cong Su; Di Guo; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2023)

Fuel-NO formation mechanism in MILD-oxy combustion of CH4/NH3 fuel blend - Zhenghong Zhao; Zewu Zhang; Xiaojian Zha; Ge Gao; Wenchao Mao; Fan Wu; Xiaoshan Li; Cong Luo; Liqi Zhang (Fuel, 2023)

Durable antibacterial and temperature regulated core-spun yarns for textile health and comfort applications - Wei Fan; Yao Zhang; Yanli Sun; Shujuan Wang; Cong Zhang; Xichen Yu; Weiting Wang; Kai Dong (Chemical Engineering Journal, 2023)

Design of bipolar polymer electrodes for symmetric Li-dual-ion batteries - Bangshuai Wei; Yan Hong; Wu Tang; Meichen Guo; Xuesong He; Chenbin Tang; Jiahui Hu; Cong Fan (Chemical Engineering Journal, 2023)

Genomic prediction of drought tolerance during seedling stage in maize using low-cost molecular markers - Ao Zhang; Shan Chen; Zhenhai Cui; Yubo Liu; Yuan Guan; Shuang Yang; Jingtao Qu; Juchao Nie; Dongdong Dang; Cong Li; Xiaomei Dong; Jinjuan Fan; et al. (Euphytica, 2022)
Drought tolerance in maize is a complex and polygenic trait, especially in the seedling stage. In plant breeding, complex genetic traits can be improved by genomic selection (GS), which has become a practical and effective breeding tool. In the present study, a natural maize population named Northeast China core population (NCCP) consisting of 379 inbred lines were genotyped with diversity arrays technology (DArT) and genotyping-by-sequencing (GBS) platforms. Target traits of seedling emergence rate (ER), seedling plant height (SPH), and grain yield (GY) were evaluated under two natural drought stress environments in northeast China. Adequate genetic variations were observed for all the target traits, but they were divergent across environments. Similarly, the heritability of the target trait also varied across years and environments, the heritabilities in 2019 (0.88, 0.82, 0.85 for ER, SPH, GY) were higher than those in 2020 (0.65, 0.53, 0.33) and cross-2-years (0.32, 0.26, 0.33). In total, three marker datasets, 11,865 SilicoDArT markers obtained from the DArT-seq platform, 7837 SNPs obtained from the DArT-seq platform, and 91,003 SNPs obtained from the GBS platform, were used for GS analysis after quality control. The results of phylogenetic trees showed that broad genetic diversity existed in the NCCP population. Genomic prediction results showed that the average prediction accuracies estimated using the DArT SNP dataset under the two-fold cross-validation scheme were 0.27, 0.19, and 0.33, for ER, SPH, and GY, respectively. The result of SilicoDArT is close to the SNPs from DArT-seq, those were 0.26, 0.22, and 0.33. For the trait with lower heritability, the prediction accuracy can be improved using the dataset filtered by linkage disequilibrium. For the same trait, the prediction accuracies estimated with two DArT marker datasets were consistently higher than that estimated with the GBS SNP dataset under the same genotyping cost. The prediction accuracy was improved by controlling population structure and marker quality, even though the marker density was reduced. The prediction accuracies were improved by more than 30% using the significant-associated SNPs. Due to the complexity of drought tolerance under the natural stress environments, multiple years of data need to be accumulated to improve prediction accuracy by reducing genotype-by-environment interaction. Modeling genotype-by-environment interaction into genomic prediction needs to be further developed for improving drought tolerance in maize. The results obtained from the present study provides valuable pathway for improving drought tolerance in maize using GS.

Integrating hydrochemical and microbial methods to identify hydraulic connections between three saltworks in southern Laizhou Bay, China - Fan Yang; Chao Jia; Wenbo Chang; Haitao Yang; Cong Wang; Qinghe Fan (Hydrogeology Journal, 2022)

Evaluation of seawater intrusion and water quality prediction in Dagu River of North China based on fuzzy analytic hierarchy process exponential smoothing method - Haitao Yang; Chao Jia; Xin Li; Fan Yang; Cong Wang; Xiao Yang (Environmental Science and Pollution Research, 2022)

Changes in antioxidant system and sucrose metabolism in maize varieties exposed to Cd - Cong Li; Yingdi Cao; Tianfeng Li; Meiyu Guo; Xinglin Ma; Yanshu Zhu; Jinjuan Fan (Environmental Science and Pollution Research, 2022)
Different maize varieties respond differentially to cadmium (Cd) stress. However, the physiological mechanisms that determine the response are not well defined. Antioxidant systems and sucrose metabolism help plants to cope with abiotic stresses, including Cd stress. The relationship of these two systems in the response to Cd stress is unclear. Seed is sensitive to Cd stress during germination. In this study, we investigated changes in the antioxidant system, sucrose metabolism, and abscisic acid and gibberellin concentrations in two maize varieties with low (FY9) or high (SY33) sensitivities to Cd under exposure to CdCl 2 (20 mg L −1 ) at different stages of germination (3, 6, and 9 days).The seed germination and seedling growth were inhibited under Cd stress. The superoxide, malondialdehyde, and proline concentrations, and the superoxide dismutase, peroxidase, catalase, and lipoxygenase activities increased compared with those of the control (CK; without Cd). The expression levels of three genes ( ZmOPR2 , ZmOPR5 , and ZmPP2C6 ) responsive to oxidative stress increased differentially in the two varieties under Cd stress. The activity of the antioxidant system and the transcript levels of oxidative stress–responsive genes were higher in the Cd-tolerant variety, FY9, than in the sensitive variety, SY33. Sucrose metabolism was increased under Cd stress compared with that of the CK and was more active in the Cd-sensitive variety, SY33. These results suggest that the antioxidant system is the first response to Cd stress in maize, and that sucrose metabolism is cooperative and complementary under exposure to Cd.

Adipose Mesenchymal Stem Cell-Derived Exosomes Promote Wound Healing Through the WNT/β-catenin Signaling Pathway in Dermal Fibroblasts - Cong Li; Yu An; Yu Sun; Fan Yang; Quanchen Xu; Zhiguo Wang (Stem Cell Reviews and Reports, 2022)
The differentiation, migration, and proliferation of skin fibroblasts are identified as key factors in cutaneous wound healing. Adipose-derived mesenchymal stem cells (ADMSCs) and their exosomes (ADMSC-Exos) have been considered as potential therapeutic tools for tissue regeneration; however, the underlying mechanisms on cutaneous wound healing are still not well understood. In this study, we successfully obtained ADMSC-Exos and found ADMSC-Exos significantly promoted the migration and proliferation of fibroblasts in a dose-dependent manner in vitro. The expression levels of COL-I and COL-III in fibroblasts treated with ADMSC-Exos were significantly increased, while the expression level of α-SMA was decreased. In addition, the enhanced protein expression of WNT2b and β-catenin confirmed the activation of the WNT/β-catenin signaling pathway and the WNT/β-catenin inhibitor (XAV939) reversed the promoting effect of ADMSC-Exos on wound healing and the β-catenin expression. Taken together, our study partially elucidates the mechanism of ADMSC-Exos in wound healing, illustrating the potential of ADMSC-Exos as a new therapeutic approach to promote skin wound healing. Graphical Abstract

Effects of dietary protein concentration on growth and anti-oxidant capacity of coho salmon Oncorhynchus kisutch (Walbaum, 1792) alevins - Cong-mei Xu; Hai-rui Yu; Qin Zhang; Ling-yao Li; Jing-jing Fan; Meng-jie Guo; Fang-hui Li; Xiang-yi Qiu; Ling-ling Shan (Aquaculture International, 2022)

Polysialic Acid Self-assembled Nanocomplexes for Neutrophil-Based Immunotherapy to Suppress Lung Metastasis of Breast Cancer - Chuizhong Fan; Cong Li; Shuang Lu; Xiaoxue Lai; Shuo Wang; Xinrong Liu; Yanzhi Song; Yihui Deng (AAPS PharmSciTech, 2022)

Influence Mechanism of Geomorphological Evolution in a Tidal Lagoon with Rising Sea Level - Cuiping Kuang; Jiadong Fan; Zhichao Dong; Qingping Zou; Xin Cong; Xuejian Han (Journal of Marine Science and Engineering, 2022)
A tidal lagoon system has multiple environmental, societal, and economic implications. To investigate the mechanism of influence of the geomorphological evolution of a tidal lagoon, the effect of critical erosion shear stress, critical deposition shear stress, sediment settling velocity, and initial bed elevation were assessed by applying the MIKE hydro- and morpho-dynamic model to a typical tidal lagoon, Qilihai Lagoon. According to the simulation results, without sediment supply, an increase of critical erosion, deposition shear stress, or sediment settling velocity gives rise to tidal networks with a stable terrain. Such an equilibrium state can be defined as when the change of net erosion has little variation, which can be achieved due to counter actions between the erosion and deposition effect. Moreover, the influence of the initial bed elevation depends on the lowest tidal level. When the initial bed elevation is below the lowest tidal level, the tidal networks tend to be fully developed. A Spearman correlation analysis indicated that the geomorphological evolution is more sensitive to critical erosion or deposition shear stress than sediment settling velocity and initial bed elevation. Exponential sea level rise contributes to more intensive erosion than the linear or the parabolic sea level rise in the long-term evolution of a tidal lagoon.

Taxonomical and functional bacterial community selection in the rhizosphere of the rice genotypes with different nitrogen use efficiencies - Wei Chen; Yan Gao; Jie Yang; Fangjun Fan; Weiguo Zhang; Jiangye Li; Cong Zhou; Gaoling Shi; Fei Tong; Guangping Fan (Plant and Soil, 2022)

Carbon, oxygen and strontium isotopes of the Mesoproterozoic Jixian System （1.6-1.4 Ga）in the southern margin of the North China Craton and the geological implications - Cong Tan; Yuanzheng Lu; Xin Li; Haonan Song; Dan Lv; Xueying Ma; Ru Fan; Shenghui Deng (International Geology Review, 2021)

Lipin1 Alleviates Autophagy Disorder in Sciatic Nerve and Improves Diabetic Peripheral Neuropathy - Meijian Wang; Min Xie; Shuyan Yu; Pan Shang; Cong Zhang; Xiaolin Han; Cuiqin Fan; Li Chen; Xianghua Zhuang; Shihong Chen (Molecular Neurobiology, 2021)

Design and Development of Tracked Sugarcane Transporter - Tao Wu; Hebin Wu; Qingting Liu; Xiaoling Liang; Qiuju Fan; Cong Xie (Sugar Tech, 2021)

An isolated similarity design method for shaking table tests on reinforced slopes - Zhi-jia Wang; Gang Fan; Li-cong Cao; Jin-yuan Chang (Journal of Mountain Science, 2021)

Experimental investigations on the tensile behaviour of granite after heating and water-cooling treatment - Fan Zhang; Cong Dai; Yuhao Zhang; Dianbin Guo; Jianfu Shao; Dawei Hu (Bulletin of Engineering Geology and the Environment, 2021)

Application Overview of Membrane Separation Technology in Coal Mine Water Resources Treatment in Western China - Fan Wang; Yu Wang; Cong Jing (Mine Water and the Environment, 2021)

Fluvastatin attenuated ischemia/reperfusion-induced autophagy and apoptosis in cardiomyocytes through down-regulation HMGB1/TLR4 signaling pathway - Hua-Sheng Ding; Jun Yang; Jian Yang; Xin Guo; Yan-Hong Tang; Yan Huang; Zhen Chen; Zhi-Xing Fan; Cong-Xin Huang (Molecular Biology Reports, 2021)

Multi-decadal trends in the tropical Pacific western boundary currents retrieved from historical hydrological observations - Shijian Hu; Xi Lu; Shihan Li; Fan Wang; Cong Guan; Dunxin Hu; Linchao Xin; Jie Ma (Science China Earth Sciences, 2021)
As large-scale ocean circulation is a key regulator in the redistribution of oceanic energy, evaluating the multi-decadal trends in the western Pacific Ocean circulation under global warming is essential for not only understanding the basic physical processes but also predicting future climate change in the western Pacific. Employing the hydrological observations of World Ocean Atlas 2018 (WOA18) from 1955 to 2017, this study calculated the geostrophic currents, volume transport and multi-decadal trends for the North Equatorial Current (NEC), the North Equatorial Countercurrent (NECC), the Mindanao Current (MC), the Kuroshio Current (KC) in the origin and the New Guinea Coastal Undercurrent (NGCUC) within tropical western Pacific Ocean over multi-decades. Furthermore, this study examined the contributions of temperature and salinity variations. The results showed significant strengthening trends in NEC, MC and NGCUC over the past six decades, which is mainly contributed by temperature variations and consistent with the tendency in the dynamic height pattern. Zonal wind stress averaged over the western Pacific Ocean in the same latitude of each current represents the decadal variation and multi-decadal trends in corresponding ocean currents, indicating that the trade wind forcing plays an important role in the decadal trend in the tropical western Pacific circulation. Uncertainties in the observed hydrological data and trends in the currents over the tropical western Pacific are also discussed. Given that the WOA18 dataset covers most of the historical hydrological sampling data for the tropical western Pacific, this paper provides important observational information on the multi-decadal trend of the large-scale ocean circulation in the western Pacific.

Systematic analysis to identify transcriptome-wide dysregulation of Alzheimer’s disease in genes and isoforms - Cong Fan; Ken Chen; Jiaxin Zhou; Ping-pui Wong; Dan He; Yiqi Huang; Xin Wang; Tianze Ling; Yuedong Yang; Huiying Zhao (Human Genetics, 2021)

Three-dimensional pore characteristics and permeability properties of calcareous sand with different particle sizes - Zhihan Fan; Cong Hu; Qianlin Zhu; Yonggang Jia; Dianjun Zuo; Zhibo Duan (Bulletin of Engineering Geology and the Environment, 2021)

Evaluation of crustal inhomogeneity parameters in the southern Longmenshan fault zone and adjacent regions - Xiao-Ping Fan; Yi-Cheng He; Cong-Jie Yang; Jun-Fei Wang (Journal of Seismology, 2020)
Broadband teleseismic waveform data from 13 earthquakes recorded by 70 digital seismic stations were selected to evaluate the inhomogeneity parameters of the crustal medium in the southern Longmenshan fault zone and its adjacent regions using the teleseismic fluctuation wavefield method. Results show that a strong inhomogeneity exists beneath the study region, which can be divided into three blocks according to its structure and tectonic deformation features. These are known as the Sichuan-Qinghai Block, the Sichuan-Yunnan Block, and the Mid-Sichuan Block. The velocity fluctuation ratios of the three blocks are approximately 5.1%, 3.6%, and 5.1% in the upper crust and 5.1%, 3.8%, and 4.9% in the lower crust. The inhomogeneity correlation lengths of the three blocks are about 10.1 km, 14.0 km, and 10.7 km in the upper crust and 11.8 km, 17.0 km, and 11.8 km in the lower crust. The differences in the crustal medium inhomogeneity beneath the Sichuan-Yunnan Block, the Sichuan-Qinghai Block, and the Mid-Sichuan Block may be related to intensive tectonic movement and material flow in the crust and upper mantle.

Synthesis of Carbon Dots by Varying Doped Elements and Application in Serine Detection - Yingying Hu; Rentian Guan; Xiaodong Shao; Cong Zhang; Xiaoyu Fan; Shuai Zhang; Min Hong; Qiaoli Yue (Journal of Fluorescence, 2020)

Early Paleozoic mantle evolution of East Kunlun Orogenic Belt in Qinghai, NW China: evidence from the geochemistry and geochronology of the Late Ordovician to Late Silurian mafic-ultramafic rocks in the Qimantag region - Xue-Peng Duan; Fan-Cong Meng; Li-Hui Jia (International Geology Review, 2020)

ClPLD5, a phospholipase gene is involved in protection of cytoskeleton stability in pollen of self-imcompatible ‘Xiangshui’ lemon (Citrus limon) - Wei Lin; Minhphu Do; Mi Wei; Xinhua He; Yuan Liu; Zhiyi Fan; Shuwei Zhang; Cong Luo; Guixiang Huang; Guibing Hu (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Overexpression of the mango MiCO gene delayed flowering time in transgenic Arabidopsis - Yuan Liu; Cong Luo; Xiu-Juan Zhang; Xin-Xi Lu; Hai-Xia Yu; Xiao-Jie Xie; Zhi-Yi Fan; Xiao Mo; Xin-Hua He (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Molecular characterization of an emerging reassortant mammalian orthoreovirus in China - Dandan Ye; Zhaoyang Ji; Hongyan Shi; Jianfei Chen; Da Shi; Liyan Cao; Jianbo Liu; Mingwei Li; Hui Dong; Zhaoyang Jing; Xiaobo Wang; Qiuge Liu; et al. (Archives of Virology, 2020)

The role of oceanic feedbacks in the 2014–2016 El Niño events as derived from ocean reanalysis data - Cong Guan; Fan Wang; Shijian Hu (Journal of Oceanology and Limnology, 2020)

Dynamic features of near-inertial oscillations in the Northwestern Pacific derived from mooring observations from 2015 to 2018 - Shijian Hu; Lingling Liu; Cong Guan; Linlin Zhang; Jianing Wang; Qingye Wang; Jie Ma; Fujun Wang; Fan Jia; Junqiao Feng; Xi Lu; Fan Wang; et al. (Journal of Oceanology and Limnology, 2020)

A novel putative betapartitivirus isolated from the plant-pathogenic fungus Rhizoctonia solani - Yi Chen; Jia En Su; Xi Yun Qin; Zhi Yong Fan; Xiao Hai Zhang; Qing Yu; Zhen Yuan Xia; Cong Ming Zou; Gao Kun Zhao; Zhong Long Lin (Archives of Virology, 2020)

Deformation characteristics and failure mechanism of a reactivated landslide in Leidashi, Sichuan, China, on August 6, 2019: an emergency investigation report - Weile Li; Bo Zhao; Qiang Xu; Fan Yang; Hao Fu; Cong Dai; Xinxin Wu (Landslides, 2020)

Atorvastatin ameliorates depressive behaviors and neuroinflammatory in streptozotocin-induced diabetic mice - Zhang Hai-Na; Yu Xu-Ben; Tang Cong-Rong; Cao Yan-Cheng; Yang Fan; Xu Lei-Mei; Sun Ruo-Lan; Ye-Zi; Wang Ye-Xuan; Liang Jing (Psychopharmacology, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Evaluation of the genetic diversity of mango (Mangifera indica L.) seedling germplasm resources and their potential parents with start codon targeted (SCoT) markers - Li Zhou; Xin-Hua He; Hai-Xia Yu; Mei-Yan Chen; Yan Fan; Xiu-Juan Zhang; Zhong-Bing Fang; Cong Luo (Genetic Resources and Crop Evolution, 2020)

Association between social health status and depressive symptoms among community-dwelling elderly adults in Zhejiang Province, China - Hong-lei Dai; Zhe-bin Yu; Liu-qing You; Min-hua Fan; Hong-wei Zhu; Dan-jie Jiang; Meng-yin Wu; Shu-juan Lin; Xiao-cong Zhang; Kun Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Characterization and complete genome sequence analysis of phage GP4, a novel lytic Bcep22-like podovirus - Ronghuan Wang; Yu Cong; Zhiqiang Mi; Hang Fan; Taoxing Shi; Hui Liu; Yigang Tong (Archives of Virology, 2019)

Iodine Nutrition and Thyroid Function in Pregnant Women Exposed to Different Iodine Sources - Yanting Chen; Wen Chen; Cong Du; Lili Fan; Wei Wang; Min Gao; Yixin Zhang; Tingkai Cui; Yunmeng Hao; Elizabeth N. Pearce; Chongdan Wang; Wanqi Zhang (Biological Trace Element Research, 2019)

Effects of multiple environmental factors on elimination of fenvalerate and its cis-trans isomers in aquaculture water - Jingwei Zhang; Chao Song; Cong Zhang; Gengdong Hu; Shunlong Meng; Liping Qiu; Limin Fan; Yao Zheng; Ying Liu; Jiazhang Chen (Environmental Science and Pollution Research, 2019)

Transformation of cadmium-associated schwertmannite and subsequent element repartitioning behaviors - Cong Fan; Chuling Guo; Meiqin Chen; Weilin Huang; Jingjing Wan; John.R. Reinfelder; Xiaofei Li; Yufei Zeng; Guining Lu; Zhi Dang (Environmental Science and Pollution Research, 2019)

The effects of air temperature and precipitation on the net primary productivity in China during the early 21st century - Qianfeng Wang; Jingyu Zeng; Song Leng; Bingxiong Fan; Jia Tang; Cong Jiang; Yi Huang; Qing Zhang; Yanping Qu; Wulin Wang; Wei Shui (Frontiers of Earth Science, 2018)

Particular Levels of Odors Released by Virgin Females Attract Conspecific Males of the Funnel-Web Spider Allagelena difficilis - Zhi-Wu Chen; Yi-Fan Zhao; Shi-Cong He; Ke-Ke Liu; Ji-He Liu; Yong-Hong Xiao (Journal of Chemical Ecology, 2018)

The removal of silver nanoparticle by titanium tetrachloride and modified sodium alginate composite coagulants: floc properties, membrane fouling, and floc recycle - Ziyang Wang; Yan Wang; Cong Yu; Yanxia Zhao; Meixia Fan; Baoyu Gao (Environmental Science and Pollution Research, 2018)

Polyphasic taxonomic characterisation of a novel strain as Pararhizobium haloflavum sp. nov., isolated from soil samples near a sewage treatment tank - Xia Shen; Yu Li; Zhe Zhao; Yi-Fan Han; Wen-Wu Zhang; Xiao-Yun Yu; Chong-Ya Zhang; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2018)

HBV X Protein induces overexpression of HERV-W env through NF-κB in HepG2 cells - Cong Liu; Lijuan Liu; Xiuling Wang; Youyi Liu; Miao Wang; Fan Zhu (Virus Genes, 2017)

Occurrence and human dietary assessment of sulfonamide antibiotics in cultured fish around Tai Lake, China - Chao Song; Le Li; Cong Zhang; Barry Kamira; Liping Qiu; Limin Fan; Wei Wu; Shunlong Meng; Gengdong Hu; Jiazhang Chen (Environmental Science and Pollution Research, 2017)

The N170 component is sensitive to face-like stimuli: a study of Chinese Peking opera makeup - Tiantian Liu; Shoukuan Mu; Huamin He; Lingcong Zhang; Cong Fan; Jie Ren; Mingming Zhang; Weiqi He; Wenbo Luo (Cognitive Neurodynamics, 2016)

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

Erratum to: Initiation and evolution of the South China Sea: an overview - Wei-dong Sun; Chiou-ting Lin; Chan-chan Zhang; Yong-bin Hu; Ming-xing Ling; Xing Ding; Cong-ying Li; He Li; Kai Wu; Wei-ming Fan (Acta Geochimica, 2016)

Community characteristics of macrobenthos in the Huanghe (Yellow River) Estuary during water and sediment discharge regulation - Zhonghua Ren; Fan Li; Jiali Wei; Shaowen Li; Zhenbo Lv; Yanjie Gao; Xuri Cong (Acta Oceanologica Sinica, 2016)

From folding to transpressional faulting: the Cenozoic Fusha structural belt in front of the Western Kunlun Orogen, northwestern Tibetan Plateau - Cong Wang; Xiao-Gan Cheng; Han-Lin Chen; Kang Li; Xiao-Gen Fan; Chun-Yang Wang (International Journal of Earth Sciences, 2016)

Energy-Use Efficiency and Economic Analysis of Sugar Beet Production in China: A Case Study in Xinjiang Province - Fan Hua; Li Yangyang; Fei Cong; Huo Peishu; Wang Kaiyong (Sugar Tech, 2016)

Phosphate Adsorption onto Granular-Acid-Activated-Neutralized Red Mud: Parameter Optimization, Kinetics, Isotherms, and Mechanism Analysis - Jie Ye; Xiangna Cong; Panyue Zhang; Erhard Hoffmann; Guangming Zeng; Yan Wu; Haibo Zhang; Wei Fan (Water, Air, & Soil Pollution, 2015)

Isolation and functional characterization of salt-stress induced RCI2-like genes from Medicago sativa and Medicago truncatula - Ruicai Long; Fan Zhang; Zhenyi Li; Mingna Li; Lili Cong; Junmei Kang; Tiejun Zhang; Zhongxiang Zhao; Yan Sun; Qingchuan Yang (Journal of Plant Research, 2015)

Seroprevalence and risk factors of Mycobacterium avium subspecies paratuberculosis infection in domestic sika deer in China - Qing-Feng Meng; Ying Li; Fan Yang; Gui-Zhi Yao; Ai-Dong Qian; Wei-Li Wang; Wei Cong (Tropical Animal Health and Production, 2015)

Modeling of Water Flow in Reclaimed Mine Spoil with Embedded Lignitic Fragments Using Hydrus-1D - Cong-an Ma; Qing-xiang Cai; Hui Wang; Ming’an Shao; Jun Fan; Zhuye Shi; Fengxi Wang (Mine Water and the Environment, 2015)

Screening of Inherited Metabolic Disorders in Infants with Infantile Spasms - Xiao-Ming Liu; Rui Li; Sheng-Zhi Chen; Yan Sang; Jiao Chen; Cong-Hai Fan (Cell Biochemistry and Biophysics, 2015)

Lysophosphatidic acid rescues bone mesenchymal stem cells from hydrogen peroxide-induced apoptosis - Xian-Yun Wang; Xue-Song Fan; Lin Cai; Si Liu; Xiang-Feng Cong; Xi Chen (Apoptosis, 2015)

Vaginal Nystatin Versus Oral Fluconazole for the Treatment for Recurrent Vulvovaginal Candidiasis - Shangrong Fan; Xiaoping Liu; Cong Wu; Lixuan Xu; Jianling Li (Mycopathologia, 2015)

Comparative quantification of oxygen release by wetland plants: electrode technique and oxygen consumption model - Haiming Wu; Jufeng Liu; Jian Zhang; Cong Li; Jinlin Fan; Xiaoli Xu (Environmental Science and Pollution Research, 2014)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

VSL#3 probiotics exerts the anti-inflammatory activity via PI3k/Akt and NF-κB pathway in rat model of DSS-induced colitis - Cong Dai; Chang-Qing Zheng; Fan-ji Meng; Zheng Zhou; Li-xuan Sang; Min Jiang (Molecular and Cellular Biochemistry, 2013)

Formation of the world's largest molybdenum metallogenic belt: a plate-tectonic perspective on the Qinling molybdenum deposits - Cong-Ying Li; Fang-Yue Wang; Xi-Luo Hao; Xing Ding; Hong Zhang; Ming-Xing Ling; Ji-Bin Zhou; Yi-Liang Li; Wei-Ming Fan; Wei-Dong Sun (International Geology Review, 2012)

Differential effects of paraoxonase 1 (PON1) polymorphisms on cancer risk: evidence from 25 published studies - Dai-Hua Fang; Cong-Hai Fan; Qiang Ji; Bo-Xiang Qi; Juan Li; Lu Wang (Molecular Biology Reports, 2012)

Estrogen modulation of peripheral pain signal transduction: involvement of P2X3 receptors - Bei Ma; Li-hua Yu; Juan Fan; Binhai Cong; Ping He; Xin Ni; Geoffrey Burnstock (Purinergic Signalling, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Porphyrin and Galactosyl Conjugated Micelles for Targeting Photodynamic Therapy - De-Qun Wu; Ze-Yong Li; Cao Li; Jian-Jun Fan; Bo Lu; Cong Chang; Si-Xue Cheng; Xian-Zheng Zhang; Ren-Xi Zhuo (Pharmaceutical Research, 2010)

Assessment of association of rs2200733 on chromosome 4q25 with atrial fibrillation and ischemic stroke in a Chinese Han population - Lisong Shi; Cong Li; Chuchu Wang; Yunlong Xia; Gang Wu; Fan Wang; Chengqi Xu; Pengyun Wang; Xiuchun Li; Dan Wang; Xin Xiong; Ying Bai; et al. (Human Genetics, 2009)

Atmospheric inorganic nitrogen deposition to a typical red soil forestland in southeastern China - Jian-Ling Fan; Zheng-Yi Hu; Ti-Jian Wang; Jing Zhou; Cong-yang-hui Wu; Xu Xia (Environmental Monitoring and Assessment, 2009)

Effects of several immunostimulants on phenoloxidase and hemocytes of the crab Charybdis japonica - Tingjun Fan; Miaomiao Yu; Lingling Yang; Zhenping Shi; Wenjie Sun; Rishan Cong; Xiuxia Yang; Guojian Jiang (Journal of Ocean University of China, 2009)

A probiotic treatment containing Lactobacillus, Bifidobacterium and Enterococcus improves IBS symptoms in an open label trial - Yu-jing Fan; Shu-jie Chen; Ying-cong Yu; Jian-min Si; Bin Liu (Journal of Zhejiang University-SCIENCE B, 2006)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Purification and characterization of hatching enzyme from flounder Paralichthys olivaceus - Zhen-Ping Shi; Ting-Jun Fan; Ri-Shan Cong; Xiao-Feng Wang; Wen-Jie Sun; Ling-Ling Yang (Fish Physiology and Biochemistry, 2006)

Effects of organic carbon sources on cell growth and eicosapentaenoic acid content of Nannochloropsis sp. - Xu Fang; Cong Wei; Cai Zhao-Ling; Ouyang Fan (Journal of Applied Phycology, 2004)

Induction of apoptosis in a flounder gill cell line by lymphocystis disease virus infection - G‐B Hu; R‐S Cong; T‐J Fan; X‐G Mei (Journal of Fish Diseases, 2004)
Lymphocystis disease virus (LCDV), a large icosahedral DNA virus classified to the iridovirus family, is the causative agent of lymphocystis, a disease which occurs in marine and freshwater fish species and is characterized by formation of papilloma‐like lesions on the surface of the skin. In vitro , LCDV infection causes flounder gill cells, an adherent cell line, to exhibit an obvious cytopathic effect (CPE). In order to test whether apoptosis is responsible for the observed CPE, cells infected with LCDV at a multiplicity of infection (m.o.i.) of 5 PFU per cell were examined at various time intervals for the appearance of apoptotic signs. Nuclear fragmentation, DNA laddering and caspase activation were observed in the infected cells at the time (i.e. 10 days post‐infection) when an intensive CPE was observed. These findings demonstrate that LCDV is capable of inducing apoptosis in vitro , which is different from the result of LCDV infection in vivo , and consequently suggest an intricate LCDV–host interaction.

Interactions between organic and inorganic carbon sources during mixotrophic cultivation of Synechococcus sp. - Ruijuan Kang; Jing Wang; Dingji Shi; Wei Cong; Zhaoling Cai; Fan Ouyang (Biotechnology Letters, 2004)

Growth and fatty acid composition of Nannochloropsis sp. grown mixotrophically in fed-batch culture - Fang Xu; Zhao-ling Cai; Wei Cong; Fan Ouyang (Biotechnology Letters, 2004)

Utilization of Nitrite as a Nitrogen Source by Botryococcus Braunii - Suling Yang; Jun Wang; Wei Cong; Zhaoling Cai; Fan Ouyang (Biotechnology Letters, 2004)

Growth characteristics and eicosapentaenoic acid production by Nannochloropsis sp. in mixotrophic conditions - Fang Xu; Han-hua Hu; Wei Cong; Zhao-ling Cai; Fan Ouyang (Biotechnology Letters, 2004)

Biooxidation of ferrous iron by immobilized Acidithiobacillus ferrooxidans in poly(vinyl alcohol) cryogel carriers - Zhong-er Long; Yunhong Huang; Zhaoling Cai; Wei Cong; Fan Ouyang (Biotechnology Letters, 2003)

A simple and low-cost airlift photobioreactor for microalgal mass culture - Zhang Xu; Zhou Baicheng; Zhang Yiping; Cai Zhaoling; Cong Wei; Ouyang Fan (Biotechnology Letters, 2002)

Comparison of photobioreactors for cultivation of Undaria pinnatifida gametophytes - Zhang Xu; Li Dapeng; Zhang Yiping; Zhang Xiaoyan; Cai Zhaoling; Cong Wei; Ouyang Fan (Biotechnology Letters, 2002)

A cone disk atomizer for production of biocompatible magnetic microcapsules for culture of anchorage-dependent mammalian cells - Xiuju Lu; Wei Cong; Fan Ouyang (Biotechnology Letters, 2002)

Response of growth and photosynthesis of marine red tide alga Heterosigma akashiwo to iron and iron stress condition - Dongxia Li; Wei Cong; Zhaoling Cai; Dingji Shi; Fan Ouyang (Biotechnology Letters, 2002)